Powder composition and composite particles
By using composite particles containing hot melting tetrafluoroethylene polymer and inorganic substances, combined with particles of fluoroethylene resin and aromatic resin, the problem of difficult to uniformly mixing the tetrafluoroethylene polymer and boron nitride particles is solved, and high electrical characteristics, low linear expansion and high heat dissipation of the molded substance are achieved.
Patent Information
- Application Number
- CN202180049486.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-03
- Filing Date
- 2021-07-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-07-19
AI Technical Summary
It is difficult to mix evenly with boron nitride particles, resulting in insufficient low linear expansion of the molded substance and poor mechanical strength.
The composite particles containing hot melting tetrafluoroethylene-based polymer and inorganic substances are used, and particles of fluoroethylene-based resin and aromatic resin are combined, and the uniform mixing of the tetrafluoroethylene-based polymer and inorganic particles is achieved through the design of a specific powder composition and composite particles.
The electrical characteristics, low linear expansion and high heat dissipation of the molded object are improved, and the mechanical strength and processability of the molded object are enhanced.
Smart Images

Figure BDA0004047788020000501
Abstract
Description
Technical Field
[0001] The present invention relates to a powder composition comprising composite particles containing a thermofusible tetrafluoroethylene polymer and an inorganic substance, and at least one of particles of at least one resin selected from fluorine-based resins and aromatic resins and inorganic particles, and also relates to composite particles comprising the above-mentioned tetrafluoroethylene polymer and a specific aromatic polymer. Background Art
[0002] In recent years, in the field of information and communication, from the viewpoint of increasing the frequency of signals and reducing the size, there is a demand for higher density of printed circuit boards used therefor.
[0003] As an insulating material for a printed circuit board, a film formed by impregnating glass cloth with a thermosetting resin or a film formed by forming an aromatic resin such as polyimide or liquid crystal polymer is used.
[0004] In addition, tetrafluoroethylene polymers, which have electrical properties superior to those of these aromatic resins, have attracted much attention, and in order to improve heat dissipation, a resin composition in which boron nitride particles are mixed with tetrafluoroethylene polymers has been proposed (see Patent Document 1). Powder compositions in which powders of aromatic resins and tetrafluoroethylene polymers are mixed, and molded products formed therefrom have also been proposed (see Patent Documents 2 to 5).
[0005] Tetrafluoroethylene-based polymers such as polytetrafluoroethylene (PTFE) are excellent in physical properties such as electrical properties, water and oil repellency, chemical resistance, and heat resistance, and are used in various industrial applications as coating agents for imparting the above properties to substrate surfaces.
[0006] On the other hand, tetrafluoroethylene polymers lack adhesiveness and adhesion, so it is required to improve their adhesion to the substrate. In Patent Document 6, from the perspective of improving its adhesion to the substrate, composite particles as a combination of tetrafluoroethylene polymer particles and adhesive polymer particles are disclosed.
[0007] Prior art literature
[0008] Patent Document 1: International Publication No. 2020 / 045260
[0009] Patent Document 2: Japanese Patent Application Publication No. 2002-265729
[0010] Patent Document 3: Japanese Patent Application Publication No. 2003-171538
[0011] Patent Document 4: Japanese Patent Application Publication No. 2003-200534
[0012] Patent Document 5: Japanese Patent Application Publication No. 2019-085061
[0013] Patent Document 6: Japanese Patent Application Publication No. 2013-227504 Summary of the invention
[0014] Technical problem to be solved by the invention
[0015] The tetrafluoroethylene polymer has low interaction with other substances and is difficult to be uniformly mixed with the boron nitride particles. Therefore, in Patent Document 1, the mixing ratio of the tetrafluoroethylene polymer and the boron nitride particles and the particle size distribution of the boron nitride particles are adjusted. As far as the inventors know, the molded product formed by the powder composition described in Patent Document 1 has insufficient low linear expansion.
[0016] In addition, the surface tension of tetrafluoroethylene polymers is low, and the molded product formed by mixing the powder of the tetrafluoroethylene polymer with the powder of the aromatic resin has difficulty in achieving the physical properties of the two polymers, not to mention the shape properties such as mechanical strength and processability, due to layer separation. As far as the inventors know, when other fillers are further blended into the powder composition, this tendency tends to become more prominent, and it is difficult to achieve the effect of blending other fillers.
[0017] According to the present inventors' knowledge, in a molded product formed from a powder composition containing tetrafluoroethylene polymer particles, fluorine resin particles and other fillers, the other fillers are difficult to disperse uniformly and the effects of incorporating the other fillers are not easily exhibited.
[0018] On the other hand, the composite particles described in Patent Document 6 still have insufficient adhesion to the substrate when forming a coating film, especially insufficient heat-resistant adhesion. Furthermore, when the composite particles are dispersed in a liquid to prepare a liquid coating agent, the dispersibility is still insufficient, and the uniformity of component distribution in the resulting molded product is likely to decrease.
[0019] The inventors of the present invention have conducted intensive research and found that, if specified composite particles are used, tetrafluoroethylene polymers and inorganic particles can be uniformly mixed even without strictly adjusting the mixing ratio and particle size distribution thereof with inorganic particles. The molded article formed from the composition of the present invention has its components uniformly dispersed, and can highly exhibit the physical properties (electrical properties, low linear expansion, high heat dissipation, etc.) based on the components.
[0020] The present inventors have also found that these technical problems can be solved by using predetermined composite particles and particles of a predetermined resin in combination.
[0021] Furthermore, the present inventors have found that composite particles containing a predetermined tetrafluoroethylene polymer and a predetermined aromatic polymer have excellent dispersion stability. Moreover, a molded product obtained from a dispersion containing the composite particles and a film extruded from the composite particles are dense and have excellent low linear expansion coefficients.
[0022] An object of the present invention is to provide a powder composition which has a high degree of freedom in selecting inorganic particles to be used together and can form a molded product such as a film having excellent physical properties (electrical properties, low linear expansion, high heat dissipation, etc.).
[0023] An object of the present invention is to provide a powder composition capable of forming a molded product such as a film having highly excellent physical properties (electrical properties, low linear expansion, etc.) based on a tetrafluoroethylene polymer, an inorganic substance, and a predetermined resin.
[0024] Another object of the present invention is to provide composite particles having excellent dispersion stability and a dispersion containing the composite particles.
[0025] Means of solving problems
[0026] The present invention has the following aspects.
[0027] <1> A powder composition comprising composite particles containing a thermofusible tetrafluoroethylene polymer and an inorganic substance, and at least one of particles of at least one resin selected from a fluorine-based resin and an aromatic resin, and inorganic particles.
[0028] <2> like <1> The powder composition, wherein the tetrafluoroethylene polymer is at least one selected from a tetrafluoroethylene polymer having a polar functional group containing a unit based on perfluoro(alkyl vinyl ether) and a tetrafluoroethylene polymer having no polar functional group containing a unit based on perfluoro(alkyl vinyl ether) in an amount of 2.0 to 5.0 mol % relative to all units.
[0029] <3> like <1> or <2> In the powder composition, the inorganic substance is silicon dioxide.
[0030] <4> like <1> ~ <3> The powder composition described in any one of the preceding claims, wherein at least a portion of the surface of the inorganic substance is surface-treated with a silane coupling agent.
[0031] <5> like <1> ~ <4> The powder composition according to any one of the preceding claims, wherein the composite particles are composite particles having the tetrafluoroethylene-based polymer as a core and the inorganic substance on the surface of the core.
[0032] <6> like <1> ~ <5> The powder composition described above, wherein the composite particles have an average particle size of 1 to 30 μm.
[0033] <7> like <1> ~ <6> The powder composition described in any one of the above, wherein in the composite particles, the inorganic substance is in a particle, spherical or scaly shape.
[0034] <8> like <1> ~ <7> The powder composition described in any one of the preceding claims, wherein in the composite particles, the tetrafluoroethylene polymer and the inorganic substance are each in a particle form.
[0035] <9> like <1> ~ <8> The powder composition described in any one of the above claims comprises the inorganic particles, wherein the inorganic particles include at least one selected from the group consisting of silicon dioxide particles and boron nitride particles.
[0036] <10> like <1> ~ <9> The powder composition described in any one of the above claims, wherein the particles contain the at least one resin, and the at least one resin is at least one aromatic resin selected from the group consisting of polyimide, polyimide amide, polyester, polyester amide, polyphenylene ether, polyphenylene sulfide, maleimide resin and epoxy resin.
[0037] <11> like <1> ~ <10> The powder composition according to any one of the preceding claims, comprising particles of the at least one resin, wherein the at least one resin is polytetrafluoroethylene or a hot-melt tetrafluoroethylene-based polymer.
[0038] <12> A composite particle comprising: a tetrafluoroethylene polymer having a melting temperature of 260 to 320° C. and an aromatic polymer having an aromatic ring content of 45% by mass or more.
[0039] <13> like <12> The composite particles, wherein the tetrafluoroethylene polymer is a tetrafluoroethylene polymer having polar functional groups containing units based on perfluoro(alkyl vinyl ether), or a tetrafluoroethylene polymer having no polar functional groups containing units based on perfluoro(alkyl vinyl ether) in an amount of 2.0 to 5.0 mol % relative to all units.
[0040] <14> like <12> In the composite particles, the aromatic polymer is a liquid crystal polyester.
[0041] <15> like <12> ~ <14> The composite particles described in any one of the preceding claims, wherein the tetrafluoroethylene-based polymer is used as a base particle, and the aromatic polymer is provided on the surface of the base particle.
[0042] Effects of the Invention
[0043] According to the present invention, a powder composition containing at least one of a tetrafluoroethylene polymer, an inorganic substance, a prescribed resin and inorganic particles can be obtained, and the powder composition has a high degree of freedom in selecting inorganic particles to be used together, and a formed product such as a film that highly exhibits excellent physical properties (electrical properties, low linear expansion, high heat dissipation, etc.) based on these components can be obtained.
[0044] According to the present invention, composite particles containing a tetrafluoroethylene polymer and an arbitrary amount of an aromatic polymer, and a dispersion liquid containing the composite particles having excellent dispersion stability can be obtained, and a laminate and a film having highly excellent properties (electrical properties, low linear expansion, etc.) based on the tetrafluoroethylene polymer and the aromatic polymer can be obtained. DETAILED DESCRIPTION
[0045] The following terms have the following meanings.
[0046] The "average particle size (D50)" is the volume-based cumulative 50% diameter of the object (particle) obtained by the laser diffraction scattering method. That is, the particle size distribution of the object is measured by the laser diffraction scattering method, and the cumulative curve is obtained with the total volume of the particle group of the object as 100%, and the particle size at the point where the cumulative volume reaches 50% on the cumulative curve.
[0047] “D90” is the volume-based cumulative 90% diameter of the object obtained in the same manner.
[0048] D50 and D90 of the object are determined by dispersing powder in water and analyzing the powder using a laser diffraction / scattering particle size distribution analyzer (LA-920 analyzer manufactured by HORIBA, Ltd.).
[0049] The “specific surface area” is a value calculated by measuring particles or powders using a gas adsorption (constant volume method) BET multipoint method, and is determined using NOVA4200e (manufactured by Quantachrome Instruments).
[0050] The “melting temperature (melting point)” is the temperature corresponding to the maximum value of the melting peak measured by differential scanning calorimetry (DSC).
[0051] The “glass transition temperature (Tg)” is a value measured by analyzing a polymer, a cured product, or an elastomer using a dynamic viscoelasticity measurement (DMA) method.
[0052] The "viscosity of the dispersion" is the viscosity measured at 25°C and 30 rpm using a B-type viscometer. The measurement was repeated 3 times, and the average of the 3 measured values was taken.
[0053] The “thixotropic ratio of the dispersion” is a value calculated by dividing the viscosity η1 measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement was repeated 3 times, and the average of the 3 measured values was taken.
[0054] The "unit" in a polymer refers to an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit directly formed by a polymerization reaction, or a unit in which a part of the unit is converted into another structure by treating the polymer. Hereinafter, the unit based on monomer a is also referred to as "monomer a unit".
[0055] The powder composition of the present invention (hereinafter also referred to as the "present composition") comprises: composite particles containing a hot-melt tetrafluoroethylene polymer (hereinafter also referred to as the "F polymer") and an inorganic substance (hereinafter also referred to as the "present composite particles"), and at least one of particles of at least one resin selected from a fluorine-based resin and an aromatic resin (hereinafter also referred to as the "prescribed resin") and inorganic particles.
[0056] The present composition (hereinafter referred to as "present composition A") comprising the present composite particles and inorganic particles can obtain a formed product such as a film in which the physical properties of the F polymer (electrical properties such as low dielectric loss tangent, etc.), the physical properties of the inorganic substance (low linear expansion, etc.), and the physical properties of the inorganic particles (low linear expansion, high heat dissipation, etc.) are balanced. The reason for this is not necessarily clear, but the following reasons are conceivable.
[0057] The F polymer can be said to be a thermoplastic polymer with high crystallinity, and has excellent physical stress resistance and heat resistance. The composite particles thereof and the inorganic substance have a predetermined hardness, so when the present composition A is melt-mixed, the composite particles collide with the inorganic particles, and are easily crushed and micronized. In addition, the composite particles formed by the combination of the F polymer and the inorganic substance are more likely to interact with the inorganic particles than the single F polymer. Therefore, it can be considered that the inorganic substance and the inorganic particles are uniformly mixed in the molten or softened F polymer. Moreover, it is considered that the above-mentioned effect is promoted because the F polymer and the inorganic substance are compounded.
[0058] As a result, it is considered that the molded product (film, etc.) formed from the present composition A has high physical properties based on the three components of the F polymer, the inorganic substance, and the inorganic particles.
[0059] The present composition (hereinafter referred to as "present composition B") comprising the present composite particles and a prescribed resin can provide a formed product such as a film in which the physical properties of the F polymer (electrical properties such as low dielectric loss tangent, etc.), the physical properties of the inorganic substance (low linear expansion, etc.), and the physical properties of the prescribed resin (low linear expansion, UV absorption, chemical resistance, heat resistance, processability, optical properties, etc.) are balanced. The reason for this is not necessarily clear, but the following reasons are conceivable.
[0060] The F polymer can be said to be a thermoplastic polymer with high crystallinity, and has excellent physical stress resistance and heat resistance. The composite particles thereof and the inorganic substance have a prescribed hardness, so when the present composition B is melt-mixed, the composite particles of the F polymer in a softened state are easily crushed by shear stress and micronized. In addition, the composite particles formed by the combination of the F polymer and the inorganic substance are easier to interact with the prescribed resin than the F polymer alone. Therefore, it can be considered that the composite particles are uniformly mixed in the melted or softened prescribed resin while micronizing. Moreover, it is considered that at this time, the F polymer and the inorganic substance are compounded and mixed as a whole with the prescribed resin in the above state.
[0061] As a result, it is considered that the molded product (film, etc.) formed from the present composition B has high physical properties based on the three components of the F polymer, the inorganic substance, and the predetermined resin.
[0062] The F polymer in the present composite particles contained in the present composition is a polymer containing units based on tetrafluoroethylene (TFE) (TFE units).
[0063] The F polymer is heat-fusible, and its melting point is preferably 260 to 320° C., more preferably 285 to 320° C. In this case, the present composite particles are easily mixed with the inorganic particles and the predetermined resin more uniformly.
[0064] The glass transition temperature of the F polymer is preferably 75 to 125°C, more preferably 80 to 100°C.
[0065] The melt viscosity of the F polymer at 380°C is preferably 1×10 2 ~1×10 6 Pa·s, more preferably 1×10 3 ~1×10 6 Pa·s.
[0066] As the F polymer, there can be mentioned a polymer containing TFE units and units based on ethylene, a polymer containing TFE units and units based on propylene, a polymer containing TFE units and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units) (PFA), a copolymer containing TFE units and units based on hexafluoropropylene (FEP), a polymer containing TFE units and units based on fluoroalkylethylene, and a polymer containing TFE units and units based on chlorotrifluoroethylene, more preferably PFA or FEP, and even more preferably PFA. The above polymers may further contain units based on other comonomers.
[0067] As PAVE, CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (also referred to as PPVE) is preferred, and PPVE is more preferred.
[0068] The polymer F preferably has a polar functional group. In this case, the molded product formed from the present composition tends to have excellent physical properties such as electrical characteristics and surface smoothness.
[0069] The polar functional group may be contained in the unit contained in the F polymer, or may be contained in the terminal group of the polymer main chain. As the latter F polymer, there may be mentioned a polymer having a polar functional group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., or a polymer having a polar functional group obtained by plasma treatment or electrolysis off-line treatment.
[0070] If the F polymer has a polar functional group, the F polymer and the inorganic substance in the present composite particles can be easily attached not only physically but also chemically, and the above-mentioned effect can be easily enhanced.
[0071] As the polar functional group, a hydroxyl-containing group, a carbonyl-containing group and a phosphonyl-containing group are preferred, a hydroxyl-containing group and a carbonyl-containing group are more preferred, and a carbonyl-containing group is further preferred.
[0072] As the hydroxyl group, an alcoholic hydroxyl group is preferred, and -CF2CH2OH, -C(CF3)2OH and 1,2-ethylene glycol group (-CH(OH)CH2OH) are more preferred.
[0073] As the carbonyl-containing group, preferred are a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-CO(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) and a carbonate group (-OC(O)O-), and more preferred is an acid anhydride residue.
[0074] Preferred forms of the F polymer include a polymer (1) having a polar functional group containing TFE units and PAVE units, or a polymer (2) having no polar functional group containing TFE units and PAVE units and containing 2.0 to 5.0 mol % of PAVE units relative to all monomer units. These polymers form microspherulites in the molded product, and thus the physical properties of the obtained molded product are easily improved.
[0075] The polymer (1) preferably contains 90 to 99 mol% of TFE units, 0.5 to 9.97 mol% of PAVE units, and 0.01 to 3 mol% of units based on a monomer having a polar functional group, based on all units.
[0076] As the monomer having a polar functional group, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH") are preferred.
[0077] Specific examples of the polymer (1) include polymers described in International Publication No. 2018 / 16644.
[0078] The polymer (2) consists only of TFE units and PAVE units, and preferably contains 95.0 to 98.0 mol % of TFE units and 2.0 to 5.0 mol % of PAVE units based on all units.
[0079] The content of the PAVE unit in the polymer (2) is preferably at least 2.1 mol %, more preferably at least 2.2 mol %, based on the total units.
[0080] The polymer (2) having no polar functional group means that the number of carbon atoms constituting the main chain of the polymer is 1×10 6 The number of polar functional groups possessed by the polymer is less than 500. The number of polar functional groups is preferably 100 or less, more preferably less than 50. The lower limit of the number of polar functional groups is usually 0.
[0081] The F polymer (2) can be produced by using a polymerization initiator or chain transfer agent that does not generate a polar functional group that becomes a terminal group of the polymer chain, or by fluorinating an F polymer having a polar functional group (a polymer having a polar functional group derived from a polymerization initiator at the terminal group of the polymer chain, etc.).
[0082] As a method of fluorination treatment, a method using fluorine gas can be mentioned (see Japanese Patent Laid-Open No. 2019-194314, etc.).
[0083] The present composite particles may contain other polymers than the polymer F. However, the proportion of the polymer F in the polymer contained in the present composite particles is preferably 80% by mass or more, more preferably 100% by mass.
[0084] Examples of the polymer other than the F polymer include heat-resistant resins such as aromatic polyester, polyamide-imide, thermoplastic polyimide, polyphenylene ether, and polyphenylene ether.
[0085] As the inorganic substance in the present composite particles contained in the present composition, oxides, nitrides, metal monomers, alloys and carbon are preferred, and silicates (silica, wollastonite, talc, mica), metal oxides (beryllium oxide, cerium oxide, aluminum oxide, basic aluminum oxide, magnesium oxide, zinc oxide, titanium oxide, etc.), boron nitride and magnesium metasilicate (talc) are more preferred, and inorganic oxides containing at least one element selected from aluminum, magnesium, silicon, titanium and zinc are further preferred, and silicon dioxide, titanium oxide, zinc oxide, talc and boron nitride are particularly preferred, and silicon dioxide is most preferred. In addition, the inorganic substance may also be ceramic. One inorganic substance may be used, or two or more inorganic substances may be mixed and used. When mixing two or more inorganic substances, two kinds of silicon dioxide may be used, or silicon dioxide and metal oxides may be used.
[0086] The interaction between the inorganic substance and the F polymer is likely to be enhanced, and the composite particles can contain more inorganic substances. In addition, in the molded product formed from the present composition, the physical properties based on the inorganic substance are likely to be prominently exhibited.
[0087] The inorganic substance in the present composite particles preferably contains silicon dioxide.
[0088] The content of silicon dioxide in the inorganic substance is preferably 50% by mass or more, more preferably 75% by mass or more, and is preferably 100% by mass or less, more preferably 90% by mass or less.
[0089] It is preferred that at least a portion of the surface of the inorganic substance is surface treated.
[0090] The surface treatment agent used in the surface treatment is preferably a silane coupling agent, and as the silane coupling agent, 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane and 3-isocyanatopropyltriethoxysilane are preferred.
[0091] The specific surface area (BET method) of the inorganic substance is preferably 1 to 20 m 2 / g, more preferably 5 to 8 m 2 In this case, the interaction between the inorganic substance and the F polymer is likely to be enhanced. Moreover, the inorganic substance, the F polymer, the inorganic particles, the inorganic substance, the F polymer, and the prescribed resin are more evenly distributed in the molded product, and the physical properties of the three are likely to be balanced.
[0092] Specific examples of inorganic substances include silica fillers (such as "admafin (registered trademark)" series manufactured by Yaduma Co., Ltd.), zinc oxide surface-treated with esters such as propylene glycol dicaprate (such as "FINEX (registered trademark)" series manufactured by Sakai Chemical Industry Co., Ltd.), spherical fused silica (such as "SFP (registered trademark)" series manufactured by Denka Co., Ltd.), rutile titanium oxide coated with polyols and inorganic substances (such as "TIPAQUE (registered trademark)" series manufactured by Ishihara Sangyo Co., Ltd.), rutile titanium oxide surface-treated with alkyl silane (such as "JMT (registered trademark)" series manufactured by Teika Co., Ltd.), and medium-sized titanium oxides. Hollow silica fillers (“E-SPHERES” series manufactured by Pacific Cement Co., Ltd., “SiliNax” series manufactured by Nippon Steel Mining Co., Ltd., “Eccospheres” series manufactured by Emerson & Cuming Co., Ltd., etc., “Aerosil” series manufactured by Japan Aerosil Co., Ltd., etc.) ) hydrophobic AEROSIL series "RX200" manufactured by Nippon Talc Co., Ltd., etc.), talc filler ("SG" series manufactured by Nippon Talc Co., Ltd., etc.), block talc filler ("BST" series manufactured by Nippon Talc Co., Ltd., etc.), boron nitride filler ("UHP" series manufactured by Showa Denko K.K., "Denka Boron Nitride" series ("GP", "HGP" grade) manufactured by Nippon Denka Co., Ltd., etc.).
[0093] The shape of the inorganic substance is preferably granular, preferably spherical, needle-shaped (fibrous) or plate (column). As the specific shape of the inorganic substance, spherical, flaky, layered, blade-shaped, almond-shaped, columnar, cockscomb-shaped, equiaxed, leaf-shaped, mica-shaped, block-shaped, flat-plate-shaped, wedge-shaped, rosette-shaped, mesh-shaped, prism-shaped can be cited, preferably spherical or flaky. If the inorganic substance of this shape is used, the inorganic substance distribution uniformity in the formed object is improved, and its function is easily improved.
[0094] The spherical inorganic material is preferably roughly spherical. The ratio of the minor diameter to the major diameter of the inorganic particles in this case is preferably above 0.5, more preferably above 0.8. The above ratio is preferably less than 1. If the roughly spherical inorganic particles of this height are used, the inorganic material, F polymer and inorganic particles, the inorganic material, F polymer and the prescribed resin are more evenly distributed in the molded product, and the physical properties of the three are more easily balanced.
[0095] The aspect ratio of the scaly inorganic material is preferably 5 or more, more preferably 10 or more. The aspect ratio is preferably 1,000 or less.
[0096] The D50 of the present composite particles is preferably 30 μm or less, more preferably 10 μm or less, further preferably 8 μm or less, and particularly preferably 6 μm or less. The D50 of the present composite particles is preferably 0.01 μm or more, more preferably 0.1 μm or more, and further preferably 1 μm or more.
[0097] Furthermore, D90 of the present composite particles is preferably 50 μm or less, more preferably 20 μm or less, and further preferably 10 μm or less.
[0098] When D50 and D90 of the composite particles are within this range, the physical properties of the obtained molded product are more likely to be improved.
[0099] As the shape of the composite particles, spherical, flaky, lamellar, blade-like, almond-like, columnar, cockscomb-like, equiaxed, leaf-like, mica-like, block-like, flat plate-like, wedge-like, rosette-like, mesh-like, prism-like, preferably spherical or flaky. If the composite particles of this shape are used, it is easy to mix more evenly with inorganic substances or prescribed resins, and the distribution uniformity of each component in the obtained molded product is improved, and its function is easy to improve.
[0100] Furthermore, when the composite particles are scaly, the average major diameter (average value of diameters in the longitudinal direction) is preferably within the above-mentioned range of D50.
[0101] The present composite particles are preferably manufactured by the following methods: a method in which particles of F polymer (hereinafter also referred to as "F powder") are made to collide with particles of an inorganic substance in a floating state at a temperature above the melting temperature of the F polymer (hereinafter also referred to as "dry method A"), a method in which F powder and particles of an inorganic substance are made to collide under pressure or shear (hereinafter also referred to as "dry method B"), a method in which a liquid composition containing F powder and particles of an inorganic substance is subjected to a shear treatment (hereinafter also referred to as "wet method"), etc.
[0102] In the dry method A, for example, F powder and inorganic particles are supplied to a high-temperature turbulent atmosphere, and stress is applied between the F powder and the inorganic particles by collision, thereby forming a composite. The dry method A is sometimes referred to as a hybridization process.
[0103] The atmosphere is formed by gas. Available gases include air, oxygen, nitrogen, argon or a mixture thereof.
[0104] The F powder and the inorganic particles may be supplied to the atmosphere together as a premixed mixture, or may be supplied to the atmosphere separately.
[0105] When the F powder and the inorganic particles are supplied to a high temperature atmosphere, it is preferred that the particles are not agglomerated with each other. As a method, a method of floating the particles in a medium (gas or liquid) can be adopted. A mixture of gas and liquid can also be used as the medium.
[0106] In the dry method A, the high-temperature turbulent atmosphere may be prepared and then the F powder and inorganic particles may be supplied therein, or the high-temperature turbulent atmosphere may be formed by suspending the F powder and inorganic particles in a medium and then heating the medium.
[0107] As an apparatus that can be used in the former case, there can be cited an apparatus that stirs particles in a cylindrical container by means of a stirring body (e.g., a stirring blade) that rotates at high speed, while clamping the particles between the inner wall of the container and the stirring body and applying stress (e.g., the "hybrid mixing system" manufactured by Nara Machinery Manufacturing Co., Ltd.).
[0108] The temperature of the atmosphere is preferably not less than the melting temperature of the F polymer, more preferably 260 to 400°C, further preferably 320 to 380°C.
[0109] When the inorganic particles contain a large number of aggregates formed by mutual aggregation of primary particles, the aggregates may be broken up before being supplied to the high temperature atmosphere.
[0110] The method for crushing the agglomerates may, for example, be a method using a jet mill, a pin mill or a hammer mill.
[0111] In the dry method B, for example, the F powder and the inorganic particles are pressed onto the inner circumference (receiving surface) of a cylindrical rotating body rotating around the central axis by centrifugal force, and the inner circumference and the inner stator arranged at a small distance from the inner circumference are used to apply a pressing force or a shearing force to the particles to make them composite. This dry method B is sometimes also called mechanical fusion treatment.
[0112] The atmosphere in the cylindrical rotating body may be an inert gas atmosphere or a reducing gas atmosphere. The temperature of the atmosphere is preferably lower than the melting temperature of the F polymer, more preferably lower than 100°C.
[0113] The distance between the inner peripheral surface of the cylindrical rotating body and the inner stator can be appropriately set according to the D50 of the F powder and the inorganic particles. The distance is usually preferably 1 to 10 mm.
[0114] The rotation speed of the cylindrical rotating body is preferably 500 to 10000 rpm. In this case, the production efficiency of the present composite particles is likely to be improved.
[0115] When the inorganic particles contain a large number of aggregates formed by mutual aggregation of primary particles, the aggregates may be broken up in the same manner as described in the above-mentioned dry method A before being supplied to the cylindrical rotating body.
[0116] Dry method B can also be carried out using a pulverizing and mixing device ("NOB" manufactured by Hosokawa Micron Co., Ltd.) having a rotating trough and pulverizing and mixing wings, wherein the rotating trough has a pulverizing and mixing chamber with an elliptical (irregular) cross-section and a rotating axis arranged in the horizontal direction, and the pulverizing and mixing wings have an elliptical (irregular) cross-section that can be rotatably inserted into the pulverizing and mixing chamber of the rotating trough, and its rotating axis is arranged to be concentric with the rotating axis of the rotating trough.
[0117] In this pulverizing and mixing device, the F powder and the inorganic particles are pressed between the short diameter portion of the pulverizing and mixing chamber and the long diameter portion of the pulverizing and mixing blades, and pressing force or shearing force is applied to the particles to form a composite.
[0118] In the pulverizing and mixing device, the rotation direction of the rotating trough and the rotation direction of the pulverizing and mixing blades are preferably opposite to each other, and the rotation speed of the rotating trough is preferably set to be slower than the rotation speed of the pulverizing and mixing blades.
[0119] In this pulverizing and mixing device, both the pulverizing and mixing chamber and the pulverizing and mixing wings have a special-shaped cross section, and the flowing F powder and inorganic particles falling due to their own weight can be repeatedly subjected to instantaneous pressing force or shearing force in the pulverizing and mixing chamber. In this way, the above particles can be pulverized and mixed in a short time while reducing the adverse effects caused by heat, so that the composite particles with the intended characteristics can be easily obtained.
[0120] In the wet method, a liquid composition can be prepared by mixing F powder, inorganic particles and a dispersion medium.
[0121] As the mixing method, the following methods can be cited: a method of adding F powder and inorganic particles together into a dispersion medium; a method of adding F powder and inorganic particles to the dispersion medium in sequence while mixing them; a method of premixing F powder and inorganic particles and then mixing the resulting mixed particles with the dispersion medium; a method of premixing F powder and the dispersion medium, and premixing inorganic particles and the dispersion medium, respectively, and then further mixing the resulting two mixed solutions, etc.
[0122] In the wet method, the liquid composition is prepared by the steps of pre-dispersing the F powder in the dispersion medium and then adding and mixing the inorganic particles as they are (directly) or in a state dispersed in the dispersion medium, or the liquid composition is prepared by the steps of pre-dispersing the inorganic particles in the dispersion medium and then adding and mixing the F powder as they are (directly) or in a state dispersed in the dispersion medium. This is advantageous from the perspective of mixing the F powder and the inorganic particles so that they are more uniformly dispersed, and is therefore preferred.
[0123] In the method of shearing the liquid composition, for example, a stirring device with a single shaft or multiple shafts having blades (stirring wings) such as propeller blades, turbine blades, paddle blades, shell blades, etc.; a disperser using a medium such as a ball mill, a pulverizer, a basket mill, a sand mill, a sand mill, a DINO grinder, a dispersion pad, an SC grinder, a nail crusher or a stirring mill; and a disperser not using a medium such as an ultrasonic homogenizer, a nano disperser, a high-pressure impact disperser, etc. can be used.
[0124] The shear treatment is preferably a high shear condition. "High shear" means stirring at a speed exceeding 300 rpm under stirring.
[0125] The shearing treatment may be started during the process of adding the inorganic particles to the dispersion containing the F powder (when preparing the liquid composition), or may be performed after the addition is completed (after the liquid composition is prepared). By continuing these shearing treatments for a sufficient time, the desired composite particles can be produced.
[0126] From the viewpoint of further improving the adhesion (bonding property) between the F powder and the inorganic particles, it is preferred that the F powder be surface treated before or simultaneously with the mixing with the inorganic particles.
[0127] Examples of the surface treatment include plasma treatment, corona discharge treatment, etching treatment, electron beam irradiation treatment, ultraviolet irradiation treatment, and ozone exposure treatment. Plasma treatment (particularly low-temperature plasma treatment) is preferred.
[0128] Furthermore, when the F polymer particles and the inorganic particles collide with each other by the dry method A and the dry method B, heat is easily and uniformly transferred to these particles, and the present particles are easily densified and sphericalized. In this case, the sphericity of the present composite particles is preferably 0.5 or more.
[0129] Preferred forms of the composite particles include a form having an F polymer as a core and an inorganic substance attached to the surface of the core (hereinafter also referred to as "form I"), and a form having an inorganic substance as a core and an F polymer attached to the surface of the core (hereinafter also referred to as "form II").
[0130] Here, the "core" refers to a core (central portion) necessary for forming the particle shape of the present composite particle, and does not refer to a main component in the composition of the present composite particle.
[0131] The attachment (inorganic matter or F polymer) attached to the core surface can only be attached to a part of the core surface, and can also be attached to its most of surface and even the whole surface. The former situation can be said to be the state that the attachment adheres to the core surface with dust shape, in other words, is formed into the state that the most parts of the core surface are exposed. The latter situation can be said to be the state that the attachment is paved with the core surface or the state that the attachment is coated with the core surface, and this composite particle can also be said to possess the core-shell structure formed by the shell of the core and the coated core.
[0132] In the case of form I, the F polymer core and the inorganic substance are preferably both in the form of particles. In this case, the inorganic substance having a higher hardness than the F polymer is exposed on the surface, thereby improving the fluidity of the composite particles and facilitating the handling thereof. In addition, it is easy to obtain a powder composition with high uniform dispersibility.
[0133] In the case of form I, the F polymer core may be composed of a single particle of the F polymer or may be composed of an aggregate of the F polymer.
[0134] In the production of the present composite particles of form I, it is preferred that the D50 of the F powder is set larger than the D50 of the inorganic particles, and the amount of the F powder is set larger than the amount of the inorganic particles. If the present composite particles are produced with such a relationship, the present composite particles of form I are easily obtained.
[0135] In the case of Form I, D50 of the F powder used in the production is preferably 20 μm or less, more preferably 8 μm or less. D50 of the F powder is preferably 0.1 μm or more, more preferably 1 μm or more.
[0136] In the case of Form I, the D50 of the inorganic particles used in the production is preferably 0.001 to 0.5 times, more preferably 0.001 to 0.3 times the D50 of the F powder. Specifically, it is preferred that the D50 of the F powder exceeds 1 μm and the D50 of the inorganic particles is 0.1 μm or less.
[0137] The amount of inorganic particles is 0.1 parts by mass or more, more preferably 1 part by mass or more, based on 100 parts by mass of the F polymer. The upper limit is preferably 50 parts by mass, more preferably 25 parts by mass, and further preferably 5 parts by mass.
[0138] In the present composite particles of the form I thus obtained, the above relationship is maintained, and the D50 of the F polymer core is greater than the D50 of the inorganic particles, and the mass of the F polymer in the present composite particles is greater than the mass of the inorganic. In this case, the surface of the F polymer core can be covered with a larger number of inorganic particles, and the present particles of the form I are formed to have a core-shell structure. In addition, in this case, the aggregation between the F polymer particles is suppressed, and it is easy to obtain the present composite particles in which the inorganic particles are attached to the core formed by the single F powder.
[0139] In form I, the particles of the inorganic substance are preferably spherical, and more preferably approximately spherical. The so-called approximately spherical means that when the particles are observed by a scanning electron microscope (SEM), the ratio of the short diameter to the long diameter is greater than 0.5, and the proportion of spherical particles is greater than 95%. In this case, the ratio of the short diameter to the long diameter of the inorganic particles is preferably greater than 0.6, and more preferably greater than 0.8. The above ratio is preferably less than 1. The "spherical" here refers not only to a spherical shape, but also includes a slightly deformed spherical shape.
[0140] By using the highly spherical inorganic particles, the inorganic substance, F polymer, inorganic particles, inorganic substance, F polymer, and predetermined resin are more evenly distributed in the molded product, and the physical properties of the three are more easily balanced.
[0141] In form I, the D50 of the inorganic particles is preferably in the range of 0.001 to 3 μm, more preferably in the range of 0.005 to 1 μm, and further preferably in the range of 0.01 to 0.1 μm. When D50 is in the above range, the handling and fluidity of the composite particles are easily improved, and the uniform dispersibility of the powder composition is also easily improved.
[0142] In addition, the particle size distribution of the inorganic particles is preferably 3 or less, and more preferably 2.9 or less, with the value of D90 / D10 as an index. Here, "D10" is measured in the same manner as D50 and D90, and is the volume-based cumulative 10% diameter of the object. A narrow particle size distribution is preferred from the perspective of easy control of the fluidity of the obtained composite particles.
[0143] In the embodiment I, at least a part of the surface of the inorganic particles is preferably surface treated, and more preferably the surface is treated with a silazane compound such as hexamethyldisilazane or a silane coupling agent. Examples of the silane coupling agent include the above-mentioned compounds.
[0144] In form I, the inorganic particles may be used alone or in combination of two or more. When two inorganic particles are used in combination, the D50 of each inorganic particle may be different from each other, and the mass ratio of the content of each inorganic particle may be appropriately set according to the desired function.
[0145] In addition, in form I, it is preferred that a portion of the inorganic particles are embedded in the F polymer core. This allows the inorganic particles to adhere more closely to the F polymer core, and the inorganic particles are less likely to fall off from the composite particles. That is, the stability of the composite particles is further improved.
[0146] In the present composite particles of form I, D50 of the F polymer core is preferably 0.1 μm or more, more preferably more than 1 μm. The upper limit thereof is preferably 100 μm, more preferably 50 μm, and even more preferably 10 μm.
[0147] In the composite particles of form I, the D50 of the inorganic particles is preferably 0.001 to 0.5 times, more preferably 0.001 to 0.3 times the D50 of the F polymer core. Specifically, it is preferred that the D50 of the F polymer core exceeds 1 μm and the D50 of the inorganic particles is 0.1 μm or less.
[0148] The proportion of the F polymer in the present particles of Form I is preferably 50 to 99% by mass, more preferably 75 to 99% by mass. The proportion of the inorganic substance is preferably 1 to 50% by mass, more preferably 1 to 25% by mass.
[0149] In addition, the ratio of the fluorine content to the inorganic element content on the surface of the composite particles of form I measured by energy dispersive X-ray spectroscopy is preferably less than 1, more preferably less than 0.5, and further preferably less than 0.1. The above ratio is preferably greater than 0. The target elements in the measurement are the four elements of carbon, fluorine, oxygen and silicon, and the ratio of each of the fluorine and silicon elements in the total (unit: atomic %) is sometimes used as the content of each element.
[0150] In other words, the composite particles of form I of this mass ratio are particles whose surfaces are highly covered with inorganic substances. Not only are the physical properties produced by the inorganic substances excellent, but the molded products formed therefrom are also likely to have highly possessed physical properties based on the inorganic substances, F polymers and inorganic particles, and the inorganic substances, polymers and specified resins.
[0151] The composite particles of form I may be further subjected to surface treatment according to the physical properties of the inorganic substance attached to the surface. As a specific example of the surface treatment, there can be cited a method of surface treating the composite particles of form I containing inorganic silicon dioxide with siloxanes (polydimethylsiloxane, etc.) or a silane coupling agent.
[0152] The surface treatment can be carried out by mixing a dispersion in which the present composite particles are dispersed with silicones or silane coupling agents, reacting the silicones or silane coupling agents, and then recovering the treated present composite particles.
[0153] As the silane coupling agent, the above-mentioned compounds having a functional group are preferred.
[0154] This method can not only adjust the amount of silica on the surface of the composite particles, but also adjust the surface properties thereof.
[0155] In the case of form II, it is preferred that at least a portion of the F polymer is melt-adhered to the surface of the inorganic core. Thereby, the adhesion of the F polymer to the inorganic core is further improved, and the F polymer is less likely to fall off from the composite particle. That is, the stability of the composite particle is further improved.
[0156] The inorganic core is preferably in a particle form. In this case, the surface of the inorganic core in the present composite particle is easily covered with the F polymer, and therefore, the aggregation of the present composite particle is easily prevented.
[0157] In the production of the present composite particles of form II, it is preferred to set the D50 of the inorganic particles to be larger than the D50 of the F powder, and to set the amount of inorganic particles to be larger than the amount of particles of the polymer F. If the present composite particles are produced with such a relationship, the present composite particles of form II can be easily obtained.
[0158] In this case, D50 of the F powder is preferably 0.001 to 0.5 times, more preferably 0.001 to 0.3 times, D50 of the inorganic particles.
[0159] The amount of the F powder is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, based on 100 parts by mass of the inorganic particles. The upper limit is preferably 50 parts by mass, more preferably 10 parts by mass.
[0160] In the present composite particles of form II thus obtained, the above relationship is maintained, and the D50 of the inorganic core is greater than the D50 of the F powder, and the mass of the inorganic substance in the present composite particles is greater than the mass of the polymer F. In this case, the surface of the inorganic core is covered with a larger amount of F powder, and the present composite particles of form II are formed to have a core-shell structure.
[0161] In the present composite particles of form II, D50 of the inorganic core is preferably 0.1 μm or more, more preferably more than 1 μm, and the upper limit thereof is preferably 30 μm, more preferably 10 μm.
[0162] The proportion of inorganic matter in the composite particles of form II is preferably 50 to 99% by mass, more preferably 60 to 90% by mass, and the proportion of F polymer is preferably 1 to 50% by mass, more preferably 10 to 40% by mass.
[0163] Examples of the inorganic particles in the present composition A include those containing the same inorganic substance as that forming the present composite particles. The inorganic particles in the present composition A may contain the same inorganic substance as that forming the present composite particles, or may contain a different inorganic substance.
[0164] The inorganic particles in the present composition A preferably include at least one selected from silicon dioxide particles and boron nitride particles.
[0165] When silica particles are used in combination, the electrical properties and low linear expansion of the molded product can be further improved. When boron nitride particles are used in combination, the electrical properties and high heat dissipation of the molded product can be further improved.
[0166] As the shape of inorganic particles, spherical, flaky, lamellar, blade-like, almond-like, columnar, cockscomb-like, equiaxed, leaf-like, mica-like, blocky, flat, wedge-like, rosette-like, mesh-like, prism-like can be enumerated, preferably spherical or flaky. If inorganic particles of this shape are used, it is possible to more evenly mix with this composite particle, so the distribution uniformity of each component in the resulting formed article is improved, and its function is easily improved.
[0167] Specifically, the silica particles are preferably spherical, preferably approximately spherical. In this case, the ratio of the minor diameter to the major diameter is preferably above 0.5, more preferably above 0.8. The above ratio is preferably less than 1. If the approximately spherical silica particles of this height are used in combination, the inorganic matter, the F polymer and the inorganic particles are more evenly distributed in the molded product, and the physical properties of the three are more easily balanced.
[0168] The D50 of the silica particles is preferably 0.1 to 20 μm, more preferably 1 to 10 μm. The silica particles having such a D50 have good fluidity and excellent handling properties.
[0169] Specific examples of the silica particles include the same silica fillers as the specific examples of the inorganic substance forming the present composite particles described above.
[0170] The boron nitride particles are preferably flaky. If flaky boron nitride particles (hexagonal boron nitride particles) are used together, the moldability of the present composition A is improved. In addition, the boron nitride particles are oriented in the molded product, and the heat dissipation of the molded product is more easily improved.
[0171] In this case, the aspect ratio of the boron nitride particles is preferably 1.0 to 3.0, more preferably 1.0 to 2.5. The D50 (corresponding to the average major diameter) thereof is preferably 1 to 25 μm, more preferably 2 to 20 μm.
[0172] The boron nitride particles preferably have a bimodal particle size distribution, and preferably contain substantially no particles having a particle size (major axis) of 30.0 μm or more (the content is 0.1 mass % or less).
[0173] Specific examples of boron nitride particles include "UHP" series (manufactured by Showa Denko K.K.), CF600 (manufactured by Momentive), FS-3 (manufactured by Mizushima Alloy Steel Co., Ltd.), and "Denka Boron Nitride" series ("GP", "HGP" grades, etc.) manufactured by Denka Co., Ltd.
[0174] The present composition A may also contain particles of other tetrafluoroethylene polymers. The particles of such tetrafluoroethylene polymers may be heat-fusible or non-heat-fusible. The tetrafluoroethylene polymer may be the same type of polymer as the F polymer constituting the present composite particles, or may be a different type of polymer.
[0175] As the tetrafluoroethylene-based polymer, polytetrafluoroethylene (PTFE) or F polymer is preferred, PFA or FEP is more preferred, and the above-mentioned polymer (1) or polymer (2) is further preferred.
[0176] When PTFE particles are used in combination, the physical properties of PTFE (electrical properties such as low dielectric loss tangent) are likely to be prominently exhibited in the obtained molded product.
[0177] The PTFE is preferably PTFE having a number average molecular weight (Mn) of 200,000 or less (low molecular weight PTFE) as calculated based on the following formula (1).
[0178] Mn=2.1×10 10 ×ΔHc -5.16 ··· (1)
[0179] In formula (1), ΔHc represents the heat of crystallization (cal / g) of PTFE measured by differential scanning calorimetry.
[0180] The Mn of the low molecular weight PTFE is preferably 100,000 or less, more preferably 50,000 or less. The Mn of the low molecular weight PTFE is preferably 10,000 or more.
[0181] When the particles of the F polymer are used in combination, a molded product in which the inorganic substance and the inorganic particles are more uniformly dispersed can be easily obtained.
[0182] The tetrafluoroethylene polymer particles may consist of the tetrafluoroethylene polymer alone, or may contain the tetrafluoroethylene polymer and other components (such as the above-mentioned resin material).
[0183] The D50 of the tetrafluoroethylene polymer particles is preferably 50 μm or less, more preferably 20 μm or less, and further preferably 8 μm or less. The D50 of the tetrafluoroethylene polymer particles is preferably 0.1 μm or more, more preferably 0.3 μm or more, and further preferably 1 μm or more.
[0184] Furthermore, D90 of the tetrafluoroethylene polymer particles is preferably less than 100 μm, more preferably 90 μm or less.
[0185] Preferred forms of the present composition A include: a combination of the present composite particles comprising a polymer (1) or a polymer (2) and silica and silica particles, a combination of the present composite particles comprising a polymer (1) or a polymer (2) and silica and boron nitride particles, a combination of the present composite particles comprising a polymer (1) or a polymer (2) and silica, silica particles and particles of the polymer (1) or polymer (2), or a combination of the present composite particles comprising a polymer (1) or a polymer (2) and silica, boron nitride particles and particles of the polymer (1) or polymer (2).
[0186] The present composition A may further comprise particles of other resins. The other resins may be thermoplastic or thermosetting.
[0187] Examples of the thermoplastic resin include aromatic elastomers such as aromatic polyimide, aromatic maleimide, styrene elastomer, and liquid crystal polyester.
[0188] Specific examples of aromatic polyimides include: “Neopulim (registered trademark)” series (manufactured by Mitsubishi Gas Chemical Corporation), “SPIXAREA (registered trademark)” series (manufactured by Somaron Corporation), “Q-PILON (registered trademark)” series (manufactured by PI Technology Institute), “WINGO” series (manufactured by Wingo Technology Co., Ltd.), “Tohmide (registered trademark)” series (manufactured by T&K Toka Co., Ltd.), “KPI-MX” series (manufactured by Kawamura Industries Co., Ltd.), and “UPIA-AT” series (manufactured by Ube Industries, Ltd.).
[0189] Examples of the liquid crystal polyester include polyester or polyester amide into which an amide bond is introduced. In the polyester or polyester amide, an imide bond, a carbonate bond, a carbodiimide bond, an isocyanate-derived bond, such as an isocyanurate bond, may be further introduced.
[0190] Examples of the liquid crystal polyester include polymers described in paragraphs
[0010] to
[0015] of JP-A-2000-248056.
[0191] Specific examples of the liquid crystal polyester include the “Laperos” series manufactured by Polyplastics Co., Ltd., the “Vetra” series manufactured by Celanese Corporation, the “UENO LCP” series manufactured by Ueno Pharmaceutical Co., Ltd., the “Sumikasuper LCP” manufactured by Sumitomo Chemical Co., Ltd., the “XYDAR” series manufactured by Solvay Specialty Polymers, the “Xydar” series manufactured by JX Nippon Mining and Oil Energy Corporation, and the “Siveras” series manufactured by Toray Industries, Ltd.
[0192] Examples of the thermosetting resin include thermosetting polyimide, polyimide precursor (polyamic acid), epoxy resin, thermosetting acrylic resin, bismaleimide resin, and thermosetting polyphenylene ether resin.
[0193] In the present composition A, the content of the present composite particles is preferably 30% by mass or more, more preferably 40% by mass or more. The upper limit of the content of the present composite particles is preferably 80% by mass or less, more preferably 70% by mass or less. If the present composition A containing the present composite particles in this amount is used, it is easy to obtain a molded product that exhibits physical properties based on each component in a balanced manner.
[0194] The present composition A is preferably produced by dry blending the components. For dry blending, a mixing device such as a tumbler, a Henschel mixer, a hopper, a Banbury mixer, a roll, a Brabender, etc. can be used.
[0195] The particles of the predetermined resin in the present composition B are particles of at least one resin selected from fluorine-based resins and aromatic resins. The particles of at least one resin are particles of at least one resin selected from particles consisting only of fluorine-based resins and particles consisting only of aromatic resins, and are different from the present composite particles.
[0196] When fluorine resin particles are used in combination, the F polymer and the fluorine resin are uniformly mixed during melt kneading of the present composition B, so that a molded product in which these and the inorganic substance are uniformly dispersed can be easily obtained. The molded product has excellent physical properties (especially electrical properties and low linear expansion) based on these three.
[0197] On the other hand, when the particles of an aromatic resin are used in combination, the physical properties based on the aromatic resin can be imparted to the molded product, and the molded product can exhibit excellent dimensional stability during, for example, immersion in a chemical liquid or heat treatment.
[0198] The fluorine-based resin may be the same type of polymer as the F polymer constituting the present composite particles, or may be a different type of polymer.
[0199] As the fluorine-based resin, PTFE or F polymer is preferred, PFA or FEP is more preferred, and the above-mentioned polymer (1) or polymer (2) is further preferred.
[0200] When PTFE particles are used in combination, the physical properties of PTFE (electrical properties such as low dielectric loss tangent) are likely to be prominently exhibited in the obtained molded product. The preferred range of the morphology of PTFE and the Mn of PTFE are as described above.
[0201] When the particles of the F polymer are used in combination, a molded product in which the inorganic substance is more uniformly dispersed can be easily obtained.
[0202] The fluorine-based resin particles may consist of the fluorine-based resin alone, or may contain the fluorine-based resin and other components (such as the above-mentioned resin material).
[0203] The preferred ranges of D50 and D90 of the fluorine-based resin particles are as described above.
[0204] In addition, the aromatic resin is preferably at least one aromatic resin selected from the group consisting of polyimide, polyimide amide, polyester, polyester amide, polyphenylene ether, polyphenylene sulfide, maleimide resin and epoxy resin. If particles of such aromatic resins are used in combination, the dimensional stability and UV absorption (UV processability) of the obtained molded product during chemical liquid immersion or heat treatment are further improved.
[0205] Among them, liquid crystalline aromatic polyesters are preferred.
[0206] Examples of the liquid crystalline aromatic polyester include aromatic polyesters or aromatic polyester amides into which amide bonds are introduced. Aromatic polyesters or aromatic polyester amides may further include bonds derived from isocyanates such as imide bonds, carbonate bonds, carbodiimide bonds, or isocyanurate bonds.
[0207] The liquid crystalline aromatic polyester is preferably thermoplastic, and its melting temperature is preferably in the range of 260 to 360°C, more preferably in the range of 270 to 350°C.
[0208] Among the liquid crystalline aromatic polyesters, the following polyesters are preferred: polyesters containing at least units based on p-hydroxybenzoic acid (HBA) or units based on 6-hydroxy-2-naphthoic acid (HNA), polyesters containing HBA units and HNA units, polyesters containing aromatic hydroxycarboxylic acid units of at least one of HBA or HNA and aromatic diol units of at least one of 4,4'-dihydroxybiphenyl or hydroquinone and aromatic dicarboxylic acid units of at least one of terephthalic acid, isophthalic acid or 2,6-naphthalene dicarboxylic acid, polyesters containing HBA units and 2,6-dihydroxynaphthoic acid units; polyesters containing 2,6-dihydroxynaphthoic acid units, terephthalic acid units and acetaminophenol units, polyesters containing HBA units, terephthalic acid units and 4,4'-bisphenol units.
[0209] These aromatic polyesters are industrially produced, and examples thereof include "Vectra" series manufactured by Celanese Corporation, "Xydar" series manufactured by JX Energy Corporation, "Laperos" series manufactured by Polyplastics Co., Ltd., and "UENO LCP" series manufactured by Ueno Pharmaceutical Co., Ltd.
[0210] D50 of the particles of the aromatic resin is preferably 0.1 to 200 μm, more preferably 1 to 100 μm, and still more preferably 5 to 50 μm.
[0211] The at least one resin is preferably a fluorine resin and an aromatic resin. That is, the present composition B is preferably a powder composition comprising the present composite particles, particles of a fluorine resin and particles of an aromatic resin. In this case, it is easy to obtain a molded product that exhibits the above-mentioned physical properties in a balanced manner.
[0212] Preferred forms of the present composition B include a combination of the present composite particles comprising polymer (1) or polymer (2) and silica, and particles of liquid crystalline aromatic polyester, or a combination of the present composite particles comprising polymer (1) or polymer (2) and silica, particles of liquid crystalline aromatic polyester, and particles of polymer (1) or polymer (2).
[0213] In the present composition B, the content of the present composite particles is preferably 1 to 90% by mass, more preferably 10 to 80% by mass, and further preferably 20 to 70% by mass. The content of the particles of the prescribed resin is preferably 10 to 99% by mass, more preferably 20 to 90% by mass, and further preferably 30 to 80% by mass. If the present composite particles and the particles of the prescribed resin are used in combination with such a content relationship, it is easy to obtain a molded product that exhibits the physical properties of each component in a balanced manner.
[0214] The present composition B is preferably produced by dry-blending the components. The above-mentioned mixing apparatus can be used for dry-blending.
[0215] The present composition is preferably used for melt extrusion molding, injection molding or compression molding.
[0216] By melt extrusion molding, for example, a film described later can be preferably produced.
[0217] By injection molding or compression molding, an antenna component capable of producing an antenna having excellent antenna gain, for example, can be suitably manufactured.
[0218] The antenna includes, for example, an antenna member formed from the present composition and an antenna pattern formed from a conductor. In particular, it is preferred that the antenna member is a holding member that holds the antenna pattern or an alignment layer that covers the antenna pattern.
[0219] When a film (hereinafter also referred to as "the present film") is formed from the present composition, melt extrusion molding is preferably carried out by a method using a T-die, and more preferably by a method in which the present composition fed from a hopper is melt-kneaded in an extruder (single-axis screw or double-axis screw) and then extruded from a T-die arranged at the front end of the extruder to form a film.
[0220] The film obtained by melt extrusion is preferably further stretched. Thus, a more isotropic film is obtained. Stretching refers to a process in which the film is softened at a temperature below the melting point and stretched in one direction (uniaxial: MD direction) or two directions (biaxial: MD direction and TD direction).
[0221] From the viewpoint of obtaining an isotropic film, the stretching treatment is more preferably a biaxial stretching treatment.
[0222] As the stretching method, an inflation method and a flat film method can be mentioned. As the flat film method, any method of simultaneous biaxial stretching or sequential biaxial stretching can be adopted.
[0223] In the production of a film by melt extrusion molding, the obtained film may be further subjected to lamination treatment, stretching treatment, cooling treatment, and peeling treatment.
[0224] The lamination treatment is a treatment in which a release film is laminated on both surfaces or on one surface of the obtained film to form a laminate.
[0225] Examples of the lamination method include a thermocompression bonding method and a surface treatment method. In this case, a thermocompression bonding roll, a thermopressing device, or a laminator can be used.
[0226] For example, when a thermocompression bonding roll is used, the obtained film and the release film are overlapped and then passed through a thermocompression bonding roll to perform thermocompression bonding.
[0227] When a heat press device is used, the obtained film and the release film may be overlapped and heat-pressed on a bottom plate of the heat press device, and then cooled.
[0228] Alternatively, a pair of thermocompression bonding rolls may be used to supply the present composition in a molten state extruded from a T-die into a gap between two release films, and a laminate may be formed in the gap between the thermocompression bonding rolls.
[0229] When forming the laminate, by using a coextrusion method using a multilayer die, a multilayer body can be formed in which the film formed from the present composition and the release film are separately layered.
[0230] The thickness of the release film is preferably 10 to 200 μm, more preferably 20 to 100 μm.
[0231] The stretching treatment is a treatment for softening the release film layer of the laminate obtained by the lamination treatment and stretching the laminate to obtain a stretched product. The stretching treatment may be performed continuously.
[0232] The cooling treatment is a treatment for cooling the stretched product obtained by the stretching treatment. The cooling may be natural cooling or using a cooling roll or the like.
[0233] The peeling treatment is a treatment for peeling the release film from the cooled stretched product. The peeling treatment can be performed by a 90° peeling method or a 180° peeling method.
[0234] By such a series of treatments, a film having a further suppressed thermal expansion coefficient can be obtained from the present composition.
[0235] Inflation molding can also be used for forming the film.
[0236] In inflation molding, the melt-kneaded product of the present composition extruded from an annular die (circular die) extends in two directions (MD direction and TD direction), so the isotropy of the film is easily improved. In inflation molding, the melt-kneaded product is mechanically stretched in two directions by stretching and expansion, so it is easy to form a film in which the molecules of the polymer are oriented in two directions.
[0237] In this case, a film having a structure similar to that of the above-mentioned laminate may be formed by inflation molding.
[0238] That is, the present composition and other thermoplastic polymers are melt-extruded from an annular die and inflation-molded to form a laminate.
[0239] Examples of the laminate that can be formed at this time include a two-layer laminate consisting of a film layer formed by the present composition and a release film layer (type 1), a three-layer laminate consisting of a film layer formed by the present composition sandwiched between two release film layers (type 2), and a three-layer laminate consisting of a release film layer sandwiched between two film layers formed by the present composition (type 3). Preferably, the laminate is of type 1 or type 3.
[0240] In these laminates, the thickness of the film layer formed from the present composition is preferably 3 to 150 μm. In addition, the thickness of the release film layer is preferably not less than but not more than twice the thickness of the above-mentioned film layer.
[0241] By such a series of treatments, a film having a further suppressed thermal expansion coefficient can be obtained from the present composition.
[0242] The present film preferably has a metal layer formed on its surface to form a metal-clad laminate. Examples of the metal include various metals such as copper, nickel, aluminum, silver, gold, and tin, and alloys thereof (such as stainless steel).
[0243] As such metal-clad laminates, there can be mentioned single-sided metal-clad laminates having a metal layer and the present film in sequence, and double-sided metal-clad laminates having a metal layer, the present film layer, and a metal layer in sequence. In addition, these metal-clad laminates may also have other layers (prepreg layers, glass component layers, ceramic component layers, other resin film layers).
[0244] As methods for forming a metal layer on the surface of the present film, there can be mentioned a method of attaching a metal foil on the surface of the present film by a lamination method or a hot pressing method, a method of forming a metal layer on the surface of the present film by a sputtering method or a vapor deposition method, a method of forming a metal layer on the surface of the present film by a plating method (including electroless plating or electrolytic plating after electroless plating), and a method of forming a metal layer on the surface of the present film by a printing method (screen printing, inkjet method, ion plating method) using a metal conductive ink.
[0245] Moreover, as a metal foil, copper foil, such as a rolled copper foil and an electrolytic copper foil, is preferable.
[0246] In order to further improve the adhesion with the metal layer, the surface of the present film may be subjected to a surface treatment. Examples of the surface treatment include plasma treatment, corona treatment, flame treatment, and ITRO treatment.
[0247] The metal-clad laminate can be used as a material or component for a printed circuit board, a high heat dissipation substrate, an antenna substrate, and the like.
[0248] For example, if the metal layer of the metal-clad laminate is etched to form a pattern circuit, a printed circuit board can be obtained. In this case, after the pattern circuit is formed, an interlayer insulating film can be formed on the pattern circuit, and the pattern circuit can be further formed on the interlayer insulating film.
[0249] A solder resist may be laminated on the pattern circuit, or a coating film may be laminated. The coating film is typically composed of a base film and an adhesive layer formed on the surface thereof, and the surface of the adhesive layer is attached to the printed circuit board. This film may also be used as a base film of the coating film. In addition, an interlayer insulating film (adhesive layer) using this film may be formed on the pattern circuit, and a polyimide film may be laminated as the coating film.
[0250] As described above, the present film has excellent low linear expansion. Specifically, the linear expansion coefficient of the present film is preferably 50 ppm / °C or less, more preferably 40 ppm / °C or less, and further preferably 30 ppm / °C or less. The lower limit of the linear expansion coefficient is 5 ppm / °C.
[0251] As described above, when the present composition contains particles of an aromatic resin, the present film can exhibit excellent dimensional stability during chemical liquid immersion or heat treatment. The dimensional stability can be evaluated based on the dimensional change of the present film before and after being cooled to 25°C after being kept at 150°C for 30 minutes. Specifically, the dimensional change rate is preferably less than 2%, more preferably less than 1.5%. The lower limit of the dimensional change rate is 0%.
[0252] The present invention also includes composite particles (hereinafter also referred to as "present particles") comprising an F polymer having a melting temperature of 260 to 320°C and an aromatic polymer having an aromatic ring content of 45% by mass or more (hereinafter also referred to as "aromatic polymer").
[0253] The present particles are a composite of the F polymer and the aromatic polymer which can contain any amount of the aromatic polymer and has high stability. The mechanism of action is not necessarily clear, but the following reasons are considered.
[0254] Compared with non-thermal-melting tetrafluoroethylene polymers, F polymers not only have excellent shape stability such as fibril resistance, but also have a high degree of freedom conformation that relaxes the restriction of molecular motion at the single molecule level. Such F polymers are easy to form microspherulites at the molecular aggregate level, and are easy to produce tiny concave-convex structures on their surfaces, and the surface area is easy to become larger. Therefore, it is believed that the molecular aggregate of F polymers, typically particles of F polymers (F powder), can be stably physically closely attached to aromatic polymers without damaging their shapes to form the present particles.
[0255] In addition, it is also believed that the aromatic ring content of the aromatic polymer is within a specific range to balance the hydrophobicity of the aromatic polymer and the F polymer, thereby improving the affinity of both. In particular, it is believed that in the case of the F polymer having the melting temperature specified in the present invention and the aromatic polymer having the aromatic ring content specified in the present invention, these tendencies act synergistically to make it easier to form the present particles.
[0256] Furthermore, it is also considered that the interaction between the tightly attached aromatic polymers further promotes the attachment of the aromatic polymers, thereby stabilizing the present particles.
[0257] As a result, it is considered that the present particles can contain an arbitrary amount of an aromatic polymer, have high stability, and highly possess the physical properties of the F polymer and the physical properties of the aromatic polymer.
[0258] The melting temperature of the polymer F in the present particles is 260 to 320° C., preferably 275 to 315° C., more preferably 290 to 310° C. Other details of the polymer F in the present particles are the same as those described above in the description of the present composition.
[0259] In this case, the affinity with aromatic polymers is easier to improve. F polymer not only has excellent particle dispersion stability, but also is easily more dense and uniformly distributed in the formed object (polymer layer, etc.) obtained by the present particles. Furthermore, it is easy to form microspherulites in the formed object, and it is easy to improve the adhesion with other components. As a result, it is easier to obtain a formed object with excellent various physical properties such as electrical properties.
[0260] The aromatic polymer constituting the present particles is characterized in that its aromatic ring content is 45% by mass or more. In this specification, "aromatic ring content" is obtained by the following formula. In addition, the carbon atoms forming the aromatic ring do not include the carbon atoms contained in the substituents bonded to the aromatic ring.
[0261] Aromatic ring content (mass %) = 100 × [mass of carbon atoms forming aromatic rings in the polymer skeleton (g) / total mass of the polymer (g)]
[0262] For example, the aromatic ring content of a typical unit contained in the liquid crystal polyester is as follows, and the aromatic ring content of each liquid crystal polyester can be calculated based on the copolymerization ratio (molar ratio) of each unit.
[0263] 2-Hydroxy-6-naphthoic acid: 71%
[0264] 4,4'-Dihydroxybiphenyl: 78%
[0265] Terephthalic acid: 54%
[0266] 2,6-Naphthalene dicarboxylic acid: 66%
[0267] The aromatic ring content of the aromatic polymer is preferably 55% by mass or more, more preferably 60% by mass or more, and further preferably 65% by mass or more. The aromatic ring content is preferably 80% by mass or less.
[0268] The aromatic ring in the aromatic polymer may be a monocyclic ring, a condensed ring, or a heterocyclic ring, and is preferably a monocyclic ring or a condensed ring.
[0269] Specific examples of the aromatic ring include a benzene ring, a naphthalene ring, an anthracene ring, and a phenanthrene ring.
[0270] The aromatic polymer may be composed of only units containing an aromatic ring, or may be composed of units containing an aromatic ring and units not containing an aromatic ring. The aromatic polymer constituting the present particles is preferably the former.
[0271] Specific examples of the aromatic polymer include polyimide, polyamide, polyamideimide, polyphenylene ether, polyphenylene sulfide, polysulfone, polyethersulfone, aromatic polyetherketone, liquid crystal polyester, etc. Among them, polyimide and liquid crystal polyester are preferred, and liquid crystal polyester is more preferred.
[0272] Examples of the liquid crystal polyester include aromatic polyesters or aromatic polyester amides into which amide bonds are introduced. Aromatic polyesters or aromatic polyester amides may further include an imide bond, a carbonate bond, a carbodiimide bond, or a bond derived from isocyanate such as an isocyanurate bond.
[0273] The liquid crystal polyester is preferably thermoplastic, and more preferably has a melting temperature in the range of 260 to 360°C, and further preferably in the range of 270 to 350°C.
[0274] As liquid crystal polyesters, there can be mentioned the polymers described in paragraphs
[0010] to
[0015] of the above-mentioned Japanese Patent Gazette No. 2000-248056. As specific examples, there can be mentioned polymers such as dicarboxylic acids (terephthalic acid, isophthalic acid, 4,4'-diphenyl ether dicarboxylic acid, acetic anhydride, etc.), dihydroxy compounds (4,4'-bisphenol, etc.), aromatic hydroxycarboxylic acids (4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 2-hydroxy-6-naphthoic acid, etc.), aromatic diamines, aromatic hydroxylamines, and aromatic aminocarboxylic acids.
[0275] Specific examples of the liquid crystal polyester include a reaction product of 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, a reaction product of 6-hydroxy-2-naphthoic acid, terephthalic acid and acetaminophen, a reaction product of 4-hydroxybenzoic acid, terephthalic acid and 4,4'-bisphenol, and a reaction product of 2-hydroxy-6-naphthoic acid, 4,4'-dihydroxybiphenyl, terephthalic acid and 2,6-naphthalenedicarboxylic acid.
[0276] Specific examples of industrially available liquid crystal polyesters include the commercially available products described above.
[0277] As the form of the present particle, there can be mentioned: a form in which the F polymer is a mother particle and an aromatic polymer is present on the surface of the mother particle, preferably a form in which the F polymer is a core and an aromatic polymer is present on the surface of the core (hereinafter also referred to as "form I'"), and a form in which the aromatic polymer is a mother particle and an F polymer is present on the surface of the mother particle, preferably an aromatic polymer is a core and an F polymer is present on the surface of the core (hereinafter also referred to as "form II'"). Here, "core" refers to the core (central part) necessary for forming the particle shape of the present particle, and does not refer to the main component in the composition of the present particle.
[0278] Aromatic polymer or F polymer on the core surface can only be attached to a part of the surface of the core, and can also be attached to most of the surface and even the whole surface of the core. The former situation can be said to be the state that the attachment is attached to the core surface with dust, in other words, is formed into the state that the most parts of the core surface are exposed. The latter situation can be said to be the state that the attachment is paved with the core surface or the state that the attachment is coated with the core surface, and this particle can also be said to possess the core-shell structure formed by the shell of the core and the coated core.
[0279] Among the present particles, the form I' is preferred. In the present particles of the form I', the F polymer is not easily denatured, and the fluidity and handling properties of the present particles are easily improved. In addition, the dispersion stability of the present particles is easily improved.
[0280] In the form I', it is preferred that the F polymer is in a particulate form (F powder) and the aromatic polymer is in a particulate form, or that the F polymer is in a particulate form and the aromatic polymer is in a non-particulate form. In other words, in the form I', the aromatic polymer may be in a particulate form covering a portion or the entire surface of the F powder, or the aromatic polymer may be in a non-particulate form covering a portion or the entire surface of the F powder.
[0281] More preferably, the F polymer core and the aromatic polymer are each in the form of particles.
[0282] In the case of Form I', the F polymer core may be composed of a single particle of F powder or may be composed of an aggregate of F powder.
[0283] In the case of form I', it is preferred that at least a portion of the aromatic polymer is bonded to the surface of the F polymer core. This further improves the adhesion of the aromatic polymer to the F polymer core and makes it less likely for the aromatic polymer to fall off from the particles. That is, the stability of the particles is further improved.
[0284] The present particles of form I' are also applicable to the preferred manufacturing methods (dry method A, dry method B, wet method) of the above-mentioned composite particles to obtain F powder and aromatic polymer particles. In this case, it is preferred to set the D50 of F powder to be larger than the D50 of aromatic polymer particles, and set the amount of F polymer to be larger than the amount of aromatic polymer. If the present particles are manufactured with such a relationship, it is easy to obtain the present particles of form I'.
[0285] The D50 of the aromatic polymer particles used in the preparation of the present particles of Form I' is preferably 0.0001 to 0.1, more preferably 0.002 to 0.02, based on the D50 of the F powder. Specifically, it is preferred that the D50 of the F powder exceeds 1 μm and the D50 of the aromatic polymer particles is 0.1 μm or less.
[0286] The amount of the aromatic polymer particles used in the preparation of the present particles of form I' is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the F powder. The upper limit is preferably 50 parts by mass, more preferably 25 parts by mass, and further preferably 5 parts by mass.
[0287] In the present particles of the form I' thus obtained, the above relationship is maintained, and the mass occupied by the F polymer is greater than the mass of the aromatic polymer. In the case where the aromatic polymer in the present particles is in the form of particles, the D50 of the F polymer core is greater than the D50 of the aromatic polymer particles. In this case, the surface of the F polymer core can be coated with a larger amount of aromatic polymer particles, and the present particles of the form I' are formed to have a core-shell structure. Moreover, in this case, the agglomeration between the F polymer particles is suppressed, and it is easy to obtain composite particles (present particles) with aromatic polymers attached to the core formed by a single F powder.
[0288] When the aromatic polymer is in the form of particles in the present particles of form I', D50 of the aromatic polymer particles is preferably in the range of 0.001 to 0.3 μm, more preferably 0.005 to 0.2 μm, and further preferably 0.01 to 0.1 μm. When D50 is within this range, the handling and flowability of the present particles are easily improved, and the dispersion stability is easily improved.
[0289] In this case, a part of the aromatic polymer particles may be embedded in the F polymer core.
[0290] In the present particles of form I', D50 of the F polymer core is 0.1 μm or more, preferably more than 1 μm, and the upper limit thereof is preferably 100 μm, more preferably 50 μm, and even more preferably 10 μm.
[0291] The proportion of the F polymer in the present particles of form I' is preferably 50 to 99% by mass, more preferably 75 to 99% by mass. The proportion of the aromatic polymer is preferably 0.1 to 50% by mass, more preferably 1 to 25% by mass.
[0292] The particles of form I' of this mass ratio, in other words, are particles whose surfaces are highly coated with an aromatic polymer. Not only are the particles having excellent physical properties (such as dispersibility in liquid) derived from the aromatic polymer excellent, but also the molded products formed therefrom are likely to have highly possessed the physical properties of the aromatic polymer and the physical properties of the F polymer.
[0293] The particles of form I' can also be further subjected to surface treatment from the perspective of adjusting their surface properties. As a specific example of the surface treatment, a method for surface treating the particles with siloxanes (polydimethylsiloxane, etc.) or silane coupling agents can be cited. The surface treatment can be implemented by mixing the dispersion dispersed with the particles and siloxanes or silane coupling agents, and recovering the particles after the siloxanes or silane coupling agents react.
[0294] In the case of form II', the F polymer is preferably in the form of particles.
[0295] In the case of form II', it is preferred that at least a portion of the F polymer is bonded to the surface of the aromatic polymer core. This further improves the adhesion of the F polymer to the aromatic polymer core and makes it less likely for the F polymer to fall off from the particles. That is, the stability of the particles is further improved.
[0296] In addition, the aromatic polymer core is preferably in a particle shape. In this case, the surface of the aromatic polymer core of the present particle is easily covered by the F polymer, thereby easily preventing the present particle from agglomerating. In addition, the aromatic polymer core can be composed of a single particle of an aromatic polymer, and can also be composed of a particle assembly of an aromatic polymer.
[0297] The present particles of form II' are also preferably manufactured by the above-mentioned dry method A, dry method B, and wet method. In this case, it is preferred that the D50 of the particles of the aromatic polymer is set to be larger than the D50 of the F powder, and the amount of the particles of the aromatic polymer is set to be more than the amount of the F powder. If such a relationship is set and the present particles are manufactured by dry method A or dry method B, it is easy to obtain the present particles of form II'.
[0298] In the case of form II', the D50 of the F powder used in the production of the present particles is preferably 0.0001 to 0.5, and more preferably 0.0002 to 0.2, based on the D50 of the particles of the aromatic polymer. In addition, the amount of the F powder is preferably 0.1 parts by mass or more, and more preferably 1 part by mass or more, relative to 100 parts by mass of the particles of the aromatic polymer. The upper limit is preferably 50 parts by mass, and more preferably 10 parts by mass.
[0299] In the present particles of the form II' thus obtained, the above relationship is maintained, and the mass of the aromatic polymer is greater than the mass of the F polymer. Moreover, when the F polymer is in a particle form, the D50 of the aromatic polymer core is greater than the D50 of the F powder. In this case, the surface of the aromatic polymer core is covered with a larger amount of F powder, and the present particles of the form II' are formed to have a core-shell structure.
[0300] In the present particles of form II', D50 of the aromatic polymer core is preferably 1 μm or more, more preferably more than 3 μm, and the upper limit thereof is preferably 40 μm, more preferably 30 μm.
[0301] In the present particles of form II', when the F polymer is in particulate form, D50 of the F powder is preferably in the range of 0.1 to 10 μm, more preferably 1 to 5 μm. When D50 is within this range, the present particles are easily handled and flowable, and the dispersion stability is easily improved.
[0302] In the present particles of form II', the proportion of the aromatic polymer is preferably 50 to 99% by mass, more preferably 60 to 90% by mass, and the proportion of the F polymer is preferably 1 to 50% by mass, more preferably 10 to 40% by mass.
[0303] The present particles may also contain inorganic particles. As inorganic particles, particles of inorganic substances in the above-mentioned present composite particles may be cited. One inorganic particle may be used, or two or more inorganic particles may be mixed. When two or more inorganic particles are mixed, two kinds of silica particles may be mixed, or silica particles and metal oxide particles may be mixed.
[0304] The interaction between the inorganic particles and the F polymer is easily enhanced, and the dispersion stability of the dispersion of the particles is more easily improved. In addition, the physical properties of the inorganic particles are easily manifested in the molded product (such as the polymer layer and film described later) formed from the dispersion.
[0305] Among them, it is preferred that the inorganic particles contain silicon dioxide. The content of silicon dioxide in the inorganic particles is preferably 80% by mass or more, more preferably 90% by mass or more. The upper limit of the content of silicon dioxide is 100% by mass.
[0306] It is preferred that at least a part of the surface of the inorganic particles is surface treated. Examples of the surface treatment agent used for the surface treatment include the above-mentioned silane coupling agents.
[0307] Specific examples and shapes of the inorganic particles are the same as those described above.
[0308] The D50 of the inorganic particles is preferably 20 μm or less, more preferably 5 μm or less, and preferably 0.001 μm or more, more preferably 0.01 μm or more.
[0309] The proportion of the inorganic particles in the present particles is preferably 0.01 to 30% by mass, more preferably 1 to 20% by mass.
[0310] The D50 of the present particles is preferably 50 μm or less, more preferably 30 μm or less, and further preferably 20 μm or less. The D50 of the present particles is preferably 0.1 μm or more, more preferably 1 μm or more, and further preferably 3 μm or more.
[0311] Furthermore, D90 of the present particles is preferably 80 μm or less, and more preferably 30 μm or less.
[0312] When D50 and D90 of the present particles are within the above ranges, the dispersion stability of the present particles in the dispersion and the physical properties of a molded product (polymer layer, etc.) obtained from the dispersion are more likely to be improved.
[0313] The present particles are preferably produced by a method in which F powder and aromatic polymer particles are caused to collide in a floating state at a temperature above the melting temperature of the F polymer (equivalent to the above-mentioned "dry method A"), or a method in which F powder and aromatic polymer particles are caused to collide in a pressed or sheared state (equivalent to the above-mentioned "dry method B").
[0314] Alternatively, the polyol may be produced by a method in which a liquid composition containing F powder and aromatic polymer particles is sheared and then the F powder is solidified (corresponding to the above-mentioned "wet method").
[0315] The F powder and the aromatic polymer particles can be supplied to the atmosphere together as a premixed mixture, or separately. In addition, in the case of obtaining the present particles containing inorganic particles, the inorganic particles can also be supplied to the atmosphere together as a premixed mixture, or the F powder and the aromatic polymer particles can be composited first, and then the inorganic particles can be supplied to the atmosphere separately. In the latter case, the present particles in the form of inorganic particles attached to at least a part of the surface or most of the surface or even the entire surface can be obtained, which is preferred from the perspective of fluidity and operability.
[0316] When the F powder and the particles of the aromatic polymer are supplied to a high temperature atmosphere, it is preferred that the particles are not agglomerated with each other. As a method, a method of floating the particles in a medium (gas or liquid) can be used. A mixture of gas and liquid can also be used as the medium.
[0317] Other details of the high-temperature turbulent atmosphere, the apparatus that can be used, etc. in the dry method A are the same as those in the production of the present composite particles described above.
[0318] The atmosphere in the cylindrical rotating body in the dry method B may be an inert gas atmosphere or a reducing gas atmosphere. The atmosphere temperature is preferably below the melting temperature of the aromatic polymer or the F polymer, more preferably below 100° C. The details of the apparatus that can be used are the same as those in the production of the composite particles described above.
[0319] In addition, when obtaining the present particle comprising inorganic particles, the inorganic particles can be further coexisted and composited, or the F powder and the aromatic polymer particles can be composited first, and then the obtained present particle and the inorganic particles can be further composited. In the latter case, the present particle having the form of inorganic particles attached to at least a portion of the surface or most of the surface or even the whole surface can be obtained, which is preferred from the perspective of fluidity and operability.
[0320] The wet method is a method of obtaining the present particles by shearing a liquid composition containing F powder and particles of an aromatic polymer to composite the F powder and particles of the aromatic polymer. In the case of obtaining the present particles containing inorganic particles, the inorganic particles may also be pre-mixed into the above-mentioned liquid composition and then sheared to composite them. In the case where the inorganic particles are silicon dioxide, colloidal silicon dioxide may be suitably used.
[0321] In the wet method, the total content of the F powder and the aromatic polymer particles in the liquid composition is preferably 20% by mass or more, more preferably 40 to 80% by mass, based on the total mass of the liquid composition.
[0322] In addition, the mass ratio of F powder to aromatic polymer particles in the liquid composition is preferably 0.01 to 2.0, with the mass of F powder being 1. More specifically, in the case of obtaining the present particles in form I', the liquid composition preferably contains 20 to 60 mass% of F powder and 1 to 20 mass% of aromatic polymer particles, and in the case of obtaining the present particles in form II', the liquid composition preferably contains 1 to 20 mass% of F powder and 20 to 60 mass% of aromatic polymer particles.
[0323] The liquid composition can be prepared by mixing F powder, aromatic polymer particles and a dispersion medium. Examples of the mixing method include: a method in which F powder and aromatic polymer particles are added and mixed into a dispersion medium together; a method in which F powder and aromatic polymer particles are added to a dispersion medium in sequence while mixing; a method in which F powder and aromatic polymer particles are pre-mixed and the resulting mixture is mixed with a dispersion medium; a method in which F powder and a dispersion medium, and aromatic polymer particles and a dispersion medium are pre-mixed separately and the resulting two mixtures are further mixed.
[0324] As the dispersion medium, the same compound as the liquid dispersion medium described below can be preferably used.
[0325] When the F powder or the particles of the aromatic polymer are mixed to obtain a liquid composition, the mixture may be stirred while mixing or after the mixing is completed. As a device for stirring, a stirring device having blades (stirring wings) such as propeller blades, turbine blades, paddle blades, and shell blades may be cited. In addition, the stirring speed at this time is sufficient as long as the F powder and the aromatic polymer particles can be effectively dispersed in the liquid composition.
[0326] Examples of methods for subjecting the liquid composition to shear treatment include: stirring by the above-mentioned stirring device or a Henschel mixer, a pressure kneader, a Banbury mixer or a planetary mixer; mixing by a disperser using a medium, such as a ball mill, a pulverizer, a basket mill, a sand mill, a sand mill, a DINO mill (a bead mill using a grinding medium such as glass beads or zirconia beads), a dispersing pad, an SC grinder, a nail crusher or a stirred mill; mixing by a disperser not using a medium, such as a high-pressure homogenizer such as a high-pressure microfluidizer, a nanodisperser, an ultimaizer disperser, an ultrasonic homogenizer, a vertical disperser, a disperser, a high-pressure impact disperser, etc.
[0327] The shear treatment is preferably a high shear condition. "High shear" has the same meaning as above.
[0328] The shearing treatment may be carried out while the F powder and the aromatic polymer particles are being mixed, or may be carried out after the mixing is completed.
[0329] The flow form of the liquid composition during the shearing treatment is preferably an upward flow. The upward flow may be an upward flow in any state of a swirling flow, an up-and-down circulation flow, or a radial flow. In addition, when forming the upward flow, the flow form may be adjusted by using a baffle or the like, or the setting position or setting angle of the treatment device (a stirrer, a stirring tank, etc.) may be adjusted to make the flow form eccentric.
[0330] When the liquid composition is sheared by forming an upward flow, the interaction between the F powder and the aromatic polymer particles during the shearing process can be easily and uniformly performed.
[0331] As a method for removing the dispersion medium after the shearing treatment to separate the present particles, heating, reduced pressure or filtration may be mentioned, and these methods may be used in combination as appropriate.
[0332] Specific examples of means for separating the particles include: (1) distilling off the dispersion medium at atmospheric pressure or under reduced pressure to concentrate, and filtering and drying as needed; (2) agglomerating the particles while adjusting the temperature of the dispersion, or coagulating and crystallizing by adding electrolytes, coagulants, coagulants, etc., and then separating and drying by filtration; (3) spraying the dispersion into a dry gas at a temperature at which the dispersion medium can volatilize, and drying and recovering the dispersion; (4) centrifuging the dispersion and then drying the dispersion, etc.
[0333] Here, examples of drying means include vacuum drying, high-frequency drying, and hot air drying.
[0334] In each of the above means (1) to (4), the dispersion may be diluted with a dispersion medium as necessary to adjust in advance the total content of the F polymer and the aromatic polymer in the dispersion.
[0335] When the particles are manufactured by the above-mentioned dry method A, dry method B, or wet method, it is preferred that the F powder is surface treated before or while being mixed with the particles of the aromatic polymer in order to further improve the adhesion (adhesion) with the aromatic polymer particles. As the surface treatment, the above-mentioned treatment can be cited.
[0336] Furthermore, when the F powder is collided with the aromatic polymer particles by the dry method A and the dry method B, heat is easily and uniformly transferred to these particles, and the present particles are easily densified and sphericalized. In this case, the sphericity of the present particles is preferably 0.93 to 0.99.
[0337] In the present particle production, the D50 of the F powder is preferably 20 μm or less, more preferably 10 μm or less. The D50 of the F powder is preferably 0.01 μm or more, more preferably 0.1 μm or more. In addition, the D90 of the F powder is preferably 10 μm or less. The F powder having D50 and D90 within this range has good fluidity and dispersibility, and it is easy to control the size of the composite particles present in the dispersion medium in the wet method so that it is not easy to settle.
[0338] The bulk density of F powder is preferably 0.15 g / m 2 More preferably, 0.20 g / m 2 The bulk density of F powder is preferably 0.50 g / m 2 Below, more preferably 0.35g / m 2 the following.
[0339] In the production of the present particles, the D50 of the aromatic polymer particles is preferably 40 μm or less, more preferably 30 μm or less. The D50 of the aromatic polymer particles is preferably 0.01 μm or more, more preferably 0.1 μm or more.
[0340] The present invention also relates to a dispersion liquid (hereinafter also referred to as "the present dispersion liquid") comprising the present particles and a liquid dispersion medium, in which the present particles are dispersed. The present particles can be stably dispersed even if they are mixed with a liquid dispersion medium in large quantities. Moreover, in a formed article (polymer layer, film, etc.) formed by the present dispersion liquid, the F polymer and the aromatic polymer are more evenly distributed, and it is easy to highly exhibit the physical properties based on the F polymer and the physical properties based on the aromatic polymer.
[0341] The liquid dispersion medium is preferably a compound that is liquid at 25° C. under atmospheric pressure. The liquid dispersion medium may be polar or non-polar, preferably polar. The liquid dispersion medium is more preferably selected from at least one of water, amides, ketones and esters. The boiling point of the liquid dispersion medium is preferably in the range of 50 to 240° C. If the liquid dispersion medium is used, the particles in the present dispersion liquid are easily kept in a stable dispersed state.
[0342] Examples of the liquid dispersion medium include water, N,N-dimethylformamide, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, N-methyl-2-pyrrolidone, γ-butyrolactone, cyclohexanone, cyclopentanone, butyl acetate, methyl isopropyl ketone, methyl ethyl ketone and toluene. Preferred are water, N-methyl-2-pyrrolidone, γ-butyrolactone, methyl ethyl ketone, cyclohexanone and cyclopentanone. More preferred are N-methyl-2-pyrrolidone and methyl ethyl ketone.
[0343] The liquid dispersion medium may be used alone or in combination of two or more.
[0344] The liquid dispersion medium can be a mixture of a fluorine-based liquid dispersion medium and a non-fluorine-based liquid dispersion medium. The total content of the fluorine-based liquid dispersion medium relative to the fluorine-based liquid dispersion medium and the non-fluorine-based liquid dispersion medium is preferably 1 to 25% by mass. As the fluorine-based liquid dispersion medium, fluoroalcohol, hydrofluoroether and hydrofluorocarbon are preferred. In this case, the present dispersion liquid easily has excellent dispersion stability.
[0345] The liquid dispersion medium may be a mixture of a liquid dispersion medium having a surface tension of 30 mN / m or less and a liquid dispersion medium having a surface tension of 20 to 50 mN / m or water. In this case, the present dispersion liquid tends to have excellent dispersion stability.
[0346] The liquid dispersion medium may be a mixture of a liquid dispersion medium having a boiling point of 80 to 260° C. and a liquid dispersion medium having an evaporation rate of 0.01 to 0.3 when the evaporation rate of butyl acetate is 1 and a boiling point of 140 to 260° C. In this case, the present dispersion liquid tends to have excellent dispersion stability.
[0347] The content of the liquid dispersion medium in the present dispersion is preferably 30 to 90% by mass, more preferably 50 to 80% by mass.
[0348] The present dispersion may or may not contain a surfactant. When the present dispersion contains a surfactant, the content thereof is preferably 1 to 15% by mass, and the surfactant is preferably nonionic.
[0349] As the surfactant, acetylene-based surfactants, silicone-based surfactants and fluorine-based surfactants are preferred. In addition, the fluorine-based surfactant is a compound having a hydrophilic part and a hydrophobic part containing a fluorine-containing organic group.
[0350] However, the present dispersion is preferably a dispersion that does not contain a fluorine-based surfactant, which has excellent dispersion stability and operability, even if it does not necessarily contain a surfactant, especially a fluorine-based surfactant, according to the above-mentioned mechanism of action. In addition, the low dielectric loss tangent of the molded product formed by the present dispersion that does not contain a fluorine-based surfactant is easy to further improve.
[0351] In addition to the particles, the present dispersion may contain other resin materials from the perspective of improving the electrical properties, adhesion, and low linear expansion of the molded product formed by the present dispersion. When the present dispersion contains other resin materials, the content thereof is preferably less than 40% by mass relative to the overall dispersion.
[0352] Examples of other resin materials include F polymers and aromatic resins. Other resin materials may be the same as the F polymer or aromatic polymer in the present particles.
[0353] As the F polymer in other resin materials, in addition to the above-mentioned F polymers, low molecular weight PTFE and modified PTFE can be mentioned. Low molecular weight PTFE or modified PTFE also includes copolymers of TFE and a very small amount of comonomer (HFP, PAVE, FAE, etc.).
[0354] When the F polymer in the present particles is the polymer (1) having a polar functional group, the other resin material is preferably PFA, and more preferably the polymer (1) having a polar functional group.
[0355] The aromatic resin in other resin materials is preferably aromatic polyimide, aromatic maleimide, polyphenylene ether, aromatic polyamic acid or aromatic elastomer (styrene elastomer, etc.). Aromatic polyimide can be thermoplastic or thermosetting, and thermoplastic aromatic polyimide is more preferred. Thermoplastic polyimide refers to a polyimide that has completed imidization and no longer undergoes imidization reaction. As aromatic polyimide, the above-mentioned polymers can be cited.
[0356] Examples of styrene elastomers include copolymers of styrene and conjugated dienes or (meth)acrylates (styrene-butadiene rubber; styrene core-shell copolymers; styrene block copolymers such as styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, hydrogenated products of styrene-butadiene-styrene block copolymers, and hydrogenated products of styrene-isoprene-styrene block copolymers, etc.), and preferred are styrene elastomers having properties of both rubber and plastic and exhibiting flexibility when plasticized by heating.
[0357] In this case, not only the adhesiveness and low linear expansion property of the molded product formed from the present dispersion are further improved, but also the liquid properties (viscosity, thixotropic ratio, etc.) of the present dispersion are balanced, and the handleability thereof is easily improved.
[0358] The present dispersion may also contain inorganic particles. As inorganic particles, the same inorganic particles as those that can constitute the present particles mentioned above can be cited. One inorganic particle can be used, or two or more inorganic particles can be mixed and used. When the present dispersion also contains inorganic particles, the content thereof is preferably in the range of 1 to 40% by mass relative to the overall dispersion, and more preferably 5 to 30% by mass. In addition, the ratio (mass ratio) of the content of inorganic particles in the present dispersion to the content of the present particles in the present dispersion in terms of mass is preferably 0.01 to 2, and more preferably 0.1 to 0.6.
[0359] In addition to the above-mentioned components, the present dispersion may further contain other components such as a thixotropy imparting agent, a viscosity modifier, a defoaming agent, a silane coupling agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, and a flame retardant, within a range that does not impair the effects of the present invention.
[0360] The viscosity of the present dispersion is preferably 50 mPa·s or more, more preferably 100 mPa·s or more, further preferably 5000 mPa·s or more, and particularly preferably 10000 mPa·s or more. The viscosity of the present dispersion is preferably 100000 mPa·s or less, more preferably 50000 mPa·s or less, and further preferably 20000 mPa·s or less. In this case, the present dispersion has excellent coating properties and can easily form a molded product (polymer layer, etc.) with any thickness.
[0361] In addition, the present dispersion having a viscosity within this range, particularly a high viscosity range, tends to exhibit highly the physical properties of the F polymer and the aromatic polymer in a molded product formed therefrom.
[0362] The thixotropic ratio of the present dispersion is preferably 1.0 or more. The thixotropic ratio of the present dispersion is preferably 3.0 or less, and more preferably 2.0 or less. In this case, the present dispersion has excellent coating properties and homogeneity, and a denser molded product (polymer layer, etc.) can be easily formed.
[0363] The content of the present particles in the present dispersion is preferably 20% by mass or more, more preferably 40 to 80% by mass, based on the total mass of the present dispersion.
[0364] The present dispersion is applied to the surface of a sheet substrate layer to form a liquid film, the liquid film is heated to remove the dispersion medium to form a dry film, and the dry film is then heated to sinter the F polymer. This can yield a laminate having a polymer layer (hereinafter also referred to as "F layer") comprising an F polymer and an aromatic polymer on the surface of the sheet substrate layer.
[0365] As the sheet base material layer, there can be cited metal substrates (metal foils such as copper, nickel, aluminum, titanium, and alloys thereof), heat-resistant resin films (films comprising one or more heat-resistant resins such as polyimide, polyarylate, polysulfone, polyarylsulfone, polyamide, polyetheramide, polyphenylene sulfide, polyaryletherketone, polyamideimide, liquid crystal polyester, and liquid crystal polyesteramide, and may be either a single-layer film or a multi-layer film), and prepregs (precursors of fiber-reinforced resin substrates).
[0366] As a method for applying the present dispersion to the surface of a sheet substrate, any method may be used as long as it can form a stable liquid film (wet film) formed of the present dispersion on the surface of the sheet substrate, and coating method, droplet spraying method, and dipping method may be mentioned, and coating method is preferred. If coating method is used, a liquid film can be efficiently formed on the surface of the substrate with simple equipment.
[0367] Examples of the coating method include spraying, roll coating, spin coating, gravure coating, micro gravure coating, gravure offset coating, knife coating, touch coating, rod coating, die coating, injection Meyer wire bar coating, and slot die coating.
[0368] When the liquid film is dried, the liquid film is heated at a temperature at which the dispersion medium volatilizes, and a dry film is formed on the surface of the sheet substrate. The heating temperature is preferably below the boiling point of the dispersion medium + 50°C, more preferably below the boiling point of the dispersion medium, and further preferably below the boiling point of the dispersion medium - 50°C. The temperature during drying is preferably 120°C to 200°C. In addition, air may be blown in the process of removing the dispersion medium.
[0369] During drying, the dispersion medium does not necessarily need to be completely volatilized, but it only needs to be volatilized to such an extent that the shape of the layer after being maintained is stable and a self-supporting film can be maintained.
[0370] When the F polymer is calcined, the dried film is preferably dried at a temperature equal to or higher than the melting temperature of the F polymer. The heating temperature is preferably 380° C. or lower, more preferably 350° C. or lower.
[0371] As each heating method, a method using a furnace, a method using a ventilation drying furnace, and a method of irradiating heat rays such as infrared rays can be mentioned. Heating can be performed under any state of normal pressure and reduced pressure. In addition, the heating atmosphere can be any one of an oxidizing gas atmosphere (oxygen, etc.), a reducing gas atmosphere (hydrogen, etc.), and an inert gas atmosphere (helium, neon, argon, nitrogen, etc.).
[0372] The heating time is preferably 0.1 to 30 minutes, more preferably 0.5 to 20 minutes.
[0373] When heating is performed under the above conditions, the F layer can be suitably formed while maintaining high productivity.
[0374] The thickness of the F layer is preferably 0.1 to 150 μm. Specifically, when the sheet substrate layer is a metal foil, the thickness of the F layer is preferably 1 to 30 μm. When the sheet substrate layer is a heat-resistant resin film, the thickness of the F layer is preferably 1 to 150 μm, more preferably 10 to 50 μm.
[0375] The peel strength between the F layer and the substrate layer is preferably 10 N / cm or more, more preferably 15 N / cm or more. The above peel strength is preferably 100 N / cm or less. If this dispersion is used, this laminate can be easily formed without damaging the physical properties of the F polymer in the F layer.
[0376] The present dispersion can be applied to only one surface of the sheet substrate layer or to both surfaces of the sheet substrate layer. The former gives a laminate having a sheet substrate layer and an F layer on one surface of the sheet substrate layer, while the latter gives a laminate having a sheet substrate layer and an F layer on both surfaces of the sheet substrate layer. The latter laminate is less likely to warp, and thus has excellent operability during processing.
[0377] Specific examples of the laminate include a metal-clad laminate having a metal foil and an F layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and F layers on both surfaces of the polyimide film.
[0378] In addition, the metal foil may also use a carrier metal foil containing two or more layers of metal foil. As a carrier metal foil, a carrier copper foil consisting of a carrier copper foil (thickness: 10 to 35 μm) and an ultra-thin copper foil (thickness: 2 to 5 μm) laminated on the carrier copper foil via a peeling layer can be cited. If the carrier copper foil is used, a fine pattern can be formed by the MSAP (modified semi-additive) method. As the above-mentioned peeling layer, it is preferably a metal layer containing nickel or chromium, or a multilayer metal layer laminated with the metal layer.
[0379] As a specific example of the metal foil with a carrier, the trade name "FUTF-5DAF-2" manufactured by Fukuda Metal Foil Powder Industry Co., Ltd. (Fukuda Metal Foil Powder Industry Co., Ltd.) can be mentioned.
[0380] Here, in order to further improve the low linear expansion property and adhesiveness of the outermost surface of the sheet substrate (the surface of the F layer on the opposite side to the substrate layer), the outermost surface may be further surface treated.
[0381] Examples of the surface treatment method include annealing treatment, corona treatment, plasma treatment, ozone treatment, excimer treatment, and silane coupling treatment.
[0382] The conditions for the annealing treatment are preferably a temperature of 120 to 180° C., a pressure of 0.005 to 0.015 MPa, and a time of 30 to 120 minutes.
[0383] Examples of the gas used in the plasma treatment include oxygen, nitrogen, rare gas (argon, etc.), hydrogen, ammonia, and vinyl acetate. These gases may be used alone or in combination of two or more.
[0384] Another substrate may be further laminated on the outermost surface of the laminate.
[0385] As other substrates, there may be mentioned a heat-resistant resin film, a prepreg which is a precursor of a fiber-reinforced resin sheet, a laminate having a heat-resistant resin film layer, or a laminate having a prepreg layer.
[0386] Prepreg is a sheet-like substrate made by impregnating a base material (such as short hemp and woven fabric) of reinforcing fibers (such as glass fibers and carbon fibers) with a thermosetting resin or a thermoplastic resin.
[0387] The heat-resistant resin film is a film containing one or more heat-resistant resins. Examples of the heat-resistant resin include the above-mentioned aromatic polymers.
[0388] As a lamination method, there is a method of heat-pressing the laminate and another substrate.
[0389] When the other substrate is a prepreg, the hot pressing conditions are preferably a temperature of 120 to 400°C, a vacuum atmosphere pressure of 20 kPa or less, and a pressurization pressure of 0.2 to 10 MPa. The laminate has an F layer with excellent electrical properties and is therefore suitable as a printed circuit board material, specifically, it can be used as a flexible metal-clad laminate or a rigid metal-clad laminate for the manufacture of printed circuit boards, and is particularly suitable as a flexible metal-clad laminate for the manufacture of flexible printed circuit boards.
[0390] A printed circuit board can be obtained by etching the metal foil of a laminated body (metal foil with F layer) whose base layer is a metal foil to form a transmission circuit. Specifically, the printed circuit board can be manufactured by a method of etching the metal foil to form a predetermined transmission circuit, or by a method of processing the metal foil into a predetermined transmission circuit using an electroplating method (semi-additive process (SAP process), MSAP process, etc.).
[0391] The printed circuit board made of the metal foil with F layer has a transmission circuit formed of metal foil and an F layer in this order. Specific examples of the structure of the printed circuit board include transmission circuit / F layer / prepreg layer, transmission circuit / F layer / prepreg layer / F layer / transmission circuit.
[0392] In the manufacture of the printed circuit board, an interlayer insulating film may be formed on the transmission circuit, a solder resist may be stacked on the transmission circuit, and a cover film may be stacked on the transmission circuit. These interlayer insulating films, solder resists, and cover films may also be formed from the present dispersion.
[0393] The present particles can be used for melt extrusion molding, injection molding, or compression molding to obtain a molded product containing the F polymer and the aromatic polymer. For example, the present particles can be melt extruded to obtain a film.
[0394] Furthermore, by melt-kneading the present particles and a fluoroolefin polymer and then extruding the mixture, a film containing the F polymer, the aromatic polymer and the fluoroolefin polymer can be obtained.
[0395] The fluoroolefin polymer to be melt-kneaded with the present particles may be the F polymer or a polymer other than the F polymer containing units derived from a fluoroolefin.
[0396] Examples of fluoroolefin polymers include PTFE, PFA, FEP, ETFE, and PVDF. PFA may be an F polymer or may be PFA other than an F polymer. PTFE is preferably low molecular weight PTFE or modified PTFE.
[0397] The fluoroolefin polymer also preferably has a polar functional group. The type and introduction method of the polar functional group, including the preferred type and introduction method, are the same as those in the above-mentioned F polymer.
[0398] The thickness of the film is preferably 5 to 150 μm, more preferably 10 to 100 μm.
[0399] The shape of the film can be a strip or a blade. The length of the long side direction of the strip film is preferably more than 100m. The upper limit of the length in the long side direction is usually 2000m. The length of the short side direction of the strip is preferably more than 1000mm, and the upper limit of the length in the short side direction is usually 3000mm.
[0400] The obtained film and the substrate layer are overlapped and then hot-pressed to obtain a laminate having a polymer layer formed of the film and a substrate layer. The hot-pressing conditions are preferably a temperature of 120 to 300° C., a vacuum atmosphere of 20 kPa or less, and a pressurized pressure of 0.2 to 10 MPa.
[0401] The configurations of the base material layer, the printed circuit board using the laminate, and the multilayer printed circuit board, including preferred configurations thereof, are the same as those described above.
[0402] According to the present invention, the present particle (composite particle) excellent in dispersibility and dispersion stability can be obtained. The above-mentioned F layer made by the present particle or the above-mentioned film and the laminate of other base materials can be used as antenna parts, printed substrates, aircraft parts, automobile parts, sports equipment, food industry products, coatings, cosmetics, etc. Specifically, it can be used as wire coating materials (wires for aircraft, etc.), electrical insulating tapes, insulating tapes for oil excavation, printed substrate materials, separation membranes (precision filtration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode adhesives (lithium secondary batteries, fuel cells, etc.), copy rollers, furniture, automotive dashboards, covers of household appliances, etc., sliding members (load bearings, sliding shafts, valves, bearings, gears, cams, conveyor belts, food conveyor belts, etc.), tools (shovels, files, awls, saws, etc.), boilers, hoppers, pipelines, ovens, barbecue molds, chutes, molds, toilets, container coating materials.
[0403] The present particles can also be effectively used as additives or modifiers for various varnishes (resists, inks, coatings, etc.) of resins such as polyimide and liquid crystal polymers, and can impart physical properties of F polymers.
[0404] As mentioned above, the powder composition, the present particles and the present dispersion liquid of the present invention have been described, but the present invention is not limited to the configurations of the above-mentioned embodiments.
[0405] For example, the powder composition, the present particles, and the present dispersion of the present invention may each be obtained by adding any other configuration to the configurations of the above-mentioned embodiments, or by replacing any configuration that exhibits the same function.
[0406] Example
[0407] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited thereto.
[0408] <Powder Composition>
[0409] 1. Preparation of Ingredients
[0410] [Polymer particles]
[0411] F Particles of polymer 1: Particles composed of a polymer having a polar functional group (melting temperature: 300° C.) containing 97.9 mol % of TFE units, 0.1 mol % of NAH units, and 2.0 mol % of PPVE units (D50: 2.0 μm)
[0412] F Particles of polymer 2: Particles composed of a polymer having no polar functional group (melting temperature: 300° C.) containing 97.5 mol % of TFE units and 2.5 mol % of PPVE units (D50: 2.6 μm)
[0413] [Inorganic particles (inorganic particles)]
[0414] Silica particles 1: spherical particles made of silica (D50: 0.03 μm)
[0415] Boron nitride particles 1: scaly particles made of boron nitride (D50: 7.0 μm)
[0416] [Specified resin particles]
[0417] Particles of a predetermined resin 1: A thermoplastic polymer obtained by reacting 2-hydroxy-6-naphthoic acid, 4,4'-dihydroxybiphenyl, terephthalic acid, and 2,6-naphthalenedicarboxylic acid in a ratio of 60 mol%, 20 mol%, 15.5 mol%, and 4.5 mol%, respectively, and the thermoplastic polymer was pulverized to obtain a powder (D50: 16 μm)
[0418] 2. Preparation of composite particles
[0419] (Production Example 1)
[0420] First, a mixture of 98 parts by mass of particles of F polymer 1 and 2 parts by mass of silica particles 1 was prepared.
[0421] Then, the mixture is put into a powder processing device (hybrid system) in which particles are stirred by stirring wings rotating at high speed in a cylindrical container, and particles are clamped between the inner wall of the container and the stirring body and stress is applied. After that, the particles of F polymer 1 and silica particles 1 are made to collide while floating in a high-temperature turbulent atmosphere, and stress is applied between them to perform a composite treatment. In addition, the temperature in the device during the treatment is maintained below 100°C in a nitrogen atmosphere, and the treatment time is 15 minutes.
[0422] The treated product obtained was a fine powder. The powder was analyzed using an optical microscope and confirmed to be composite particles α having a core-shell structure, with the F polymer 1 as a core and the silica particles 1 attached to the surface of the core to form a shell.
[0423] The composite particle α was spherical in shape, and its D50 was 4 μm.
[0424] (Production Example 2)
[0425] N-methyl-2-pyrrolidone and particles of polymer F 1 (98 parts by mass) were added to a tank equipped with a stirring blade, and stirred for 10 minutes to prepare a liquid composition in which particles of polymer F 1 were dispersed.
[0426] Thereafter, silica particles 1 (2 parts by mass) were added, and the mixture was stirred at 800 rpm for 15 minutes in the tank, and shear treatment was performed in a state where an upward flow was formed, thereby obtaining a dispersion.
[0427] Next, N-methyl-2-pyrrolidone was removed from the dispersion to recover fine powder, which was analyzed using an optical microscope to confirm that it was composite particles β having a core-shell structure with F polymer 1 as a core and silica particles 1 attached to the surface of the core to form a shell.
[0428] The D50 of the composite particle β was 10 μm.
[0429] (Production Example 3)
[0430] Composite particles γ were obtained in the same manner as in Example 1 except that the particles of F polymer 1 were changed to particles of F polymer 2. D50 of composite particles γ was 6 μm.
[0431] 3. Preparation of powder composition
[0432] (Powder compositions 1 to 3)
[0433] 70 parts by mass of each of the composite particles α to γ and 30 parts by mass of the boron nitride particles 1 were mixed using a Henschel mixer to prepare powder compositions 1 to 3.
[0434] (Powder composition 4)
[0435] 70 parts by mass of the composite particles α, 15 parts by mass of the boron nitride particles 1, and 15 parts by mass of the particles of the F polymer 2 were mixed using a Henschel mixer to prepare a powder composition 4.
[0436] (Powder composition 5)
[0437] 68.6 parts by mass of the particles of the F polymer 1, 1.4 parts by mass of the silica particles 1, and 30 parts by mass of the boron nitride particles 1 were mixed using a Henschel mixer to prepare a powder composition 5.
[0438] (Powder Compositions 6 to 8)
[0439] 70 parts by mass of each of the composite particles α to γ and 30 parts by mass of the particles 1 of a predetermined resin were mixed using a Henschel mixer to prepare powder compositions 6 to 8.
[0440] (Powder composition 9)
[0441] 70 parts by mass of the composite particles α, 15 parts by mass of the particles 1 of the predetermined resin, and 15 parts by mass of the particles of the F polymer 2 were mixed using a Henschel mixer to prepare a powder composition 9 .
[0442] (Powder composition 10)
[0443] 68.6 parts by mass of the particles of the F polymer 1, 1.4 parts by mass of the silica particles 1, and 30 parts by mass of the particles 1 of a predetermined resin were mixed using a Henschel mixer to prepare a powder composition 10 .
[0444] 4. Determination of linear expansion coefficient
[0445] Each of the powder compositions 1 to 5 was melt-kneaded using a twin-screw extruder (“KZW15TW-45MG” manufactured by Technovel Co., Ltd.), and then extruded from a T-die to prepare films (thickness: 100 μm) 1 to 5.
[0446] A square test piece of 180 mm square was cut out from the obtained film, and the linear expansion coefficient of the test piece in the range of 25° C. to 260° C. was measured according to the measurement method specified in JIS C 6471:1995.
[0447] [Evaluation criteria]
[0448] 0: 30ppm / ℃ or less.
[0449] △: more than 30 ppm / °C and less than 50 ppm / °C.
[0450] ×: Exceeding 50 ppm / °C.
[0451] As a result, films 1, 2, and 4 were rated "○", film 3 was rated "△", and film 5 was rated "×".
[0452] 5. Evaluation of dimensional stability
[0453] Each of the powder compositions 1 to 5 was melt-kneaded using a twin-screw extruder (“KZW15TW-45MG” manufactured by Technovel Corporation), and then extruded from a T-die to form films (thickness: 100 μm) 6 to 10 .
[0454] The dimensional change rate of the obtained film before and after the holding was measured as follows, and the evaluation was performed according to the following criteria: The evaluation of the dimensional stability of the film was based on JIS C 6481:1996.
[0455] A 30 cm square sample was cut out from the obtained film.
[0456] A line segment of 25 cm in length was drawn on the surface of the sample, and punched holes were formed with both ends of the line segment as the center.
[0457] The sample was subjected to heat treatment by heating at 150°C for 30 minutes and then cooling to 25°C. The distance between the centers of the two punched holes was measured before and after the heat treatment, and the absolute value of the expansion and contraction rate of the film during the heat treatment was taken as the dimensional change rate.
[0458] [Evaluation criteria]
[0459] ○: Dimensional change rate is less than 1.5%
[0460] △: Dimensional change rate is 1.5% or more and 2% or less
[0461] ×: Dimensional change rate exceeds 2%
[0462] As a result, films 6, 7, and 9 were "○", film 8 was "△", and film 10 was "×".
[0463] <Composite particles comprising F polymer and aromatic polymer>
[0464] [F powder]
[0465] F powder 1: particles composed of a polymer having an acid anhydride group (melting temperature: 300° C.) containing 97.9 mol % of TFE units, 0.1 mol % of NAH units, and 2.0 mol % of PPVE units (average particle size 2 μm, bulk density 0.18 g / m 2 )
[0466] F powder 2: particles composed of a polymer having no functional group (melting temperature: 305°C) containing 97.5 mol% of TFE units and 2.5 mol% of PPVE units (average particle size 2 μm, bulk density 0.19 g / m 2 )
[0467] F powder 3: particles composed of non-thermal-fusible PTFE (average particle size 0.3 μm, bulk density 0.2 g / m 2 )
[0468] [Aromatic polymer]
[0469] Aromatic powder 1: A thermoplastic polymer 1 (aromatic ring content: 69 mass %) is obtained by reacting 2-hydroxy-6-naphthoic acid, 4,4'-dihydroxybiphenyl, terephthalic acid and 2,6-naphthalenedicarboxylic acid in a ratio of 60 mol %, 20 mol %, 15.5 mol % and 4.5 mol % in sequence. The thermoplastic polymer 1 (aromatic ring content: 69 mass %) is crushed to obtain a powder (D50: 20 μm).
[0470] Aromatic powder 2: powder of aromatic polymer 2 (aromatic ring content: 40 mass%) (D50: 18 μm)
[0471] [Inorganic particles]
[0472] Inorganic particles 1: Spherical particles composed of silicon dioxide surface treated with a silane coupling agent (D50: 0.03 μm)
[0473] [Dispersion medium]
[0474] NMP: N-methyl-2-pyrrolidone
[0475] [Example 1-1]
[0476] 1. Preparation of composite particles
[0477] A mixture of 99 parts by mass of F powder 1 and 1 part by mass of aromatic powder 1 was prepared.
[0478] Then, the mixture is put into a powder processing device (mechanical fusion device) having a cylindrical rotating body with a receiving surface on the inner circumference and an inner stator arranged at a small distance from the receiving surface. After that, the cylindrical rotating body is rotated at a high speed around the central axis. The centrifugal force generated at this time is used to press the particles onto the receiving surface, and the mixture is introduced into the narrow space (pressing space) between the receiving surface and the inner stator, so that the particles collide in a shear state and are processed.
[0479] The treated product obtained was a fine powder. The powder was analyzed using an optical microscope and confirmed to be composite particles 1 having F polymer 1 as a base particle and aromatic powder 1 attached to the surface of the base particle. D50 of composite particles 1 was 25 μm.
[0480] 2. Preparation and evaluation of dispersion
[0481] 150 parts by mass of NMP was added to a tank equipped with a stirring blade, and the tank was stirred thoroughly. Next, 100 parts by mass of the obtained composite particles 1 were added to the tank and stirred for 10 minutes to obtain a dispersion 1 in which the composite particles 1 were dispersed. The viscosity of the obtained dispersion 1 was 12000 mPa·s.
[0482] The state of the dispersion 1 immediately after preparation and the state after storage in a container at 25° C. for 3 hours were visually confirmed, and the dispersion stability was evaluated according to the following criteria.
[0483] <Evaluation Criteria for Dispersion Stability>
[0484] 0: There is little foaming immediately after preparation and after storage, no agglomerates are found, and the dispersion is uniform
[0485] △: Some aggregates were observed both immediately after preparation and after storage.
[0486] ×: Many aggregates, not evenly dispersed
[0487] 3. Preparation and evaluation of laminates
[0488] The dispersion 1 was applied to the surface of the long copper foil by a bar coater to form a wet film. Next, the metal foil formed with the wet film was passed through a drying furnace at 110°C for 5 minutes and dried by heating to obtain a dry film. Then, the dry film was heated at 380°C for 3 minutes in a nitrogen furnace. Thus, a laminate having a metal foil and a polymer layer (20 μm thick) on the surface thereof as a molten product of F powder 1 and a molded product of aromatic polymer 1 was obtained.
[0489] A 180 mm square test piece was cut out from the laminate 1 , and the linear expansion coefficient of the test piece in the range of 25° C. to 260° C. was measured by the measurement method specified in JIS C 6471:1995, and evaluated according to the following criteria.
[0490] <Evaluation criteria for linear expansion coefficient>
[0491] 0: Linear expansion coefficient is below 50ppm / ℃
[0492] △: Linear expansion coefficient exceeds 50ppm / ℃ and is below 75ppm / ℃
[0493] ×: Linear expansion coefficient exceeds 75ppm / ℃
[0494] [Example 1-2~Example 1-6]
[0495] Composite particles 2 to 6 and dispersions 2 to 6 were obtained in the same manner as in Example 1-1, except that the types and amounts of the components were changed as shown in Table 1 below, to produce laminates 2 to 6.
[0496] Table 1 shows the evaluation results of the obtained dispersion and laminate.
[0497]
Table 1
[0498]
[0499] Industrial Applicability
[0500] The powder composition of the present invention can be used to produce a molded product having the physical properties of each component based on the F polymer, inorganic matter and inorganic particles, and particles of at least one resin selected from fluorine-based resins and aromatic resins. The powder molded product of the present invention can be used as antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, coatings, cosmetics, etc., and can be specifically used as wire coating materials (wires for aircraft, etc.), electrical insulating tapes, insulating tapes for oil drilling, materials for printed circuit boards, separation membranes (precision filtration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode binders (for lithium secondary batteries, fuel cells, etc.), copy rollers, covers for furniture, automobile dashboards, home appliances, etc., sliding members (load bearings, sliding shafts, valves, bearings, gears, cams, conveyor belts, food conveyor belts, etc.), tools (shovels, files, awls, saws, etc.), boilers, hoppers, pipes, ovens, barbecue molds, chutes, molds, toilets, and container coating materials.
[0501] In addition, the composite particles of the present invention comprising a specific tetrafluoroethylene polymer and a specific aromatic polymer have excellent dispersion stability and can be easily processed into films, fiber-reinforced films, prepregs, and metal laminates (metal foil with resin) as a dispersion liquid. The obtained processed articles can be used as materials for antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, sliding bearings, etc.
[0502] Furthermore, such composite particles can be effectively used as additives or modifiers for various varnishes (resists, inks, coatings, etc.).
Claims
1. A powder composition, comprising: composite particles containing a thermofusible tetrafluoroethylene polymer having a melting temperature of 260 to 320° C. and an inorganic substance, particles of at least one resin selected from a fluorine resin and an aromatic resin, and optional inorganic particles, wherein the tetrafluoroethylene polymer is a tetrafluoroethylene polymer having polar functional groups and containing units based on perfluoro(alkyl vinyl ether), the composite particles are composite particles having the tetrafluoroethylene polymer as a core and the inorganic substance attached to the surface of the core, or composite particles having the inorganic substance as a core and the tetrafluoroethylene polymer attached to the surface of the core, the content of the composite particles is 20 to 70% by mass, and the content of the particles of the at least one resin is 30 to 80% by mass.
2. The powder composition according to claim 1, wherein The inorganic substance is silicon dioxide.
3. The powder composition according to claim 1 or 2, wherein At least a portion of the surface of the inorganic substance is surface treated with a silane coupling agent.
4. The powder composition according to claim 1 or 2, wherein The composite particles are composite particles having the tetrafluoroethylene polymer as a core and the inorganic substance on the surface of the core.
5. The powder composition according to claim 1 or 2, wherein The average particle size of the composite particles is 1 to 30 μm.
6. The powder composition according to claim 1 or 2, wherein In the composite particles, the inorganic substance is in the form of particles, spheres or scales.
7. The powder composition according to claim 1 or 2, wherein In the composite particles, the tetrafluoroethylene polymer and the inorganic substance are each in a particle form.
8. The powder composition according to claim 1 or 2, wherein The inorganic particles are included, and the inorganic particles include at least one selected from the group consisting of silicon dioxide particles and boron nitride particles.
9. The powder composition according to claim 1 or 2, wherein The particles contain the at least one resin, wherein the aromatic resin is at least one selected from the group consisting of polyimide, polyimide amide, polyester, polyester amide, polyphenylene ether, polyphenylene sulfide, maleimide resin and epoxy resin.
10. The powder composition according to claim 1 or 2, wherein The particles contain the at least one resin, wherein the fluorine-based resin is polytetrafluoroethylene or a hot-melt tetrafluoroethylene-based polymer.
Citation Information
Patent Citations
Production of liquid crystalline polymer
JP2000248056A
Fluororesin composition for electronic part
JP2002265729A
Liquid crystal polyester resin composition
JP2003171538A
Fluororesin laminate and method for manufacture thereof
JP2003200534A
Composite particle, powder coating material, coating film, laminate, and method for producing composite particle
JP2013227504A